Transparent Sheet

A transparent sheet with a dual resin layer system maintains high transparency and low heat generation, addressing the non-combustibility and aesthetic challenges of existing smoke-proof walls.

JP7624253B2Active Publication Date: 2025-01-30UNITIKA LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023217138
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-12-22
Publication Date
2025-01-30
Estimated Expiration
2039-08-23

AI Technical Summary

Technical Problem

Existing transparent smoke-proof walls made of glass fiber fabric and resin compositions fail to meet non-combustibility standards while maintaining high transparency, as increasing resin weight to reduce heat generation leads to decreased transparency and higher haze.

Method used

A transparent sheet comprising a first resin layer impregnated in glass fiber fabric and a second resin layer with a higher bromine concentration than the first, ensuring a refractive index match, achieving transparency of 85% or more and haze of 10% or less, with a total heat generation of 8 MJ/m² or less.

Benefits of technology

The solution maintains high transparency and reduces total heat generation, allowing for thicker smoke-proof walls with increased resin weight without compromising aesthetics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007624253000004
    Figure 0007624253000004
  • Figure 0007624253000005
    Figure 0007624253000005
  • Figure 0007624253000006
    Figure 0007624253000006
Patent Text Reader

Abstract

To provide a transparent sheet including a glass fiber fabric and a resin which achieves improvement of transparency and reduction in a total calorific value when a resin weight is large, and a smokeproof vertical wall hanging wall using the transparent sheet.SOLUTION: A transparent sheet including a plain-woven glass fiber fabric and a resin contains a first resin layer contained in a state of being impregnated in the glass fiber fabric and a second resin layer contained in a state of being non-impregnated in the glass fiber fabric in a thickness direction of the transparent sheet, in which bromine concentration of the second resin layer is higher than bromine concentration of the first resin layer, and a total light transmittance of the transparent sheet is 85% or more and a haze is 10% or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a transparent sheet, and more particularly to a transparent sheet suitable for a suspended smoke barrier or the like, and a suspended smoke barrier using the same. [Background technology]

[0002] The Building Standards Act and its Enforcement Order prescribe that smoke exhaust systems must be installed to prevent the flow of smoke and toxic gases that are generated in the event of a fire in a building, and to facilitate evacuation and firefighting activities. Therefore, office buildings, commercial facilities, and other buildings often have smoke barriers and other equipment installed as smoke exhaust and smoke blocking systems.

[0003] Smoke-proof vertical walls are usually attached to the ceilings of buildings in order to temporarily block the flow of smoke, toxic gases, etc., to corridors and upper floors in the event of a fire, and to secure the time required for evacuation. For this reason, transparent plate glass, transparent resin composites of glass fibers and resins, etc. are used as smoke-proof vertical walls so that the smoke-proof vertical walls do not obstruct the view or spoil the aesthetics. Transparent resin composites of glass fibers and resins have the advantage of being less likely to break than transparent plate glass. For example, Patent Document 1 discloses a transparent non-combustible sheet containing a glass fiber fabric and a cured resin layer.

[0004] Patent Document 2 discloses a non-flammable sheet having at least one glass fiber fabric and a photocurable resin impregnated into the glass fiber fabric, wherein the difference in refractive index between a glass composition constituting the glass fibers in the glass fiber fabric and the photocurable resin is 0.02 or less, the ratio of the glass fiber fabric to the non-flammable sheet is 20 to 70% by weight, the ratio of the photocurable resin to the non-flammable sheet is 80 to 30% by weight, and the photocurable resin is obtained by curing a composition containing at least a brominated vinyl ester. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2005-319746 A [Patent Document 2] JP 2014-213489 A Summary of the Invention [Problem to be solved by the invention]

[0006] The Building Standards Act requires that smoke barriers be made of non-combustible materials. The requirements for certification of non-combustible materials include a total heat release of 8MJ / m2 for 20 minutes after the start of heating in a specified heat release test. 2 The maximum heat generation rate must be 200kw / m or less for 10 seconds or more within the first 20 minutes of heating. 2 The total calorific value mentioned above is the amount of resin contained in the sheet (g / m 2 ) tends to be higher.

[0007] For example, in Patent Document 1, Example 2 shows a resin amount of 300 g / m 2 The total calorific value is 8.74 MJ / m 2 As a result, the requirements for the certification test of the above-mentioned non-combustible materials are not met.

[0008] On the other hand, in Patent Document 2, a photocurable resin obtained by curing a composition containing a brominated vinyl ester is used as the photocurable resin impregnated into a glass fiber fabric, and the resin weight is increased to 200 g / m 2 This is said to solve the problem of not being able to obtain non-flammable certification if the resin weight is more than 380±10g / m. 2 Example 1: 260±7 g / m 2 and Example 2, which was 140±5 g / m 2 The total calorific value is 5.0 MJ / m 2 , 3.0MJ / m 2 , 2.0MJ / m 2 However, in the literature, the resin weight was 400 g / m2 The problem is that the above range is not certified as non-combustible.

[0009] In addition, the present inventors have found that when the resin weight of the sheet in Patent Document 2 is increased from Example 3 to Example 2 and Example 1, in order to reduce the total heat generation amount, it is necessary to simultaneously increase the weight of the glass fiber fabric. In fact, in Patent Document 2, the glass fiber fabric weight is 50 g / m in Example 3. 2 In Example 2, the thickness was 100 g / m 2 , and 150 g / m in Example 1 2 With the increase in resin weight, the weight of the glass fiber fabric is also increased, which increases the total heat generation to 8MJ / m 2 The inventors have found that the weight of the glass fiber fabric can be set as follows. The inventors have also found that there is a problem in that the haze of the obtained sheet increases with an increase in the weight of the glass fiber fabric, and the transparency of the sheet decreases. Therefore, the invention disclosed in Patent Document 2 has a problem in that, when the resin weight is increased, it is still insufficient to improve the transparency of the sheet and to reduce the total heat generation.

[0010] Therefore, the present invention aims to solve the above problems and provide a transparent sheet and a smoke-proof hanging wall using the transparent sheet, which can better achieve both improved transparency and low total heat generation when the resin weight is increased in a sheet containing glass fiber fabric and resin. [Means for solving the problem]

[0011] In order to solve the above problem, the present inventors have further studied the invention of Patent Document 2 in detail. In the invention disclosed in Patent Document 2, a brominated vinyl ester is impregnated into a glass fiber fabric to form a photocurable resin, and the difference in refractive index between the glass fiber fabric and the photocurable resin is reduced to achieve transparency. However, in the invention of Patent Document 2, in order to reduce the refractive index difference, the content of the brominated vinyl ester in the photocurable resin is limited, and it is necessary to contain a component other than the brominated vinyl ester, and it has been found that when the resin weight is increased, it is still insufficient to improve the transparency of the sheet and to reduce the total heat generation. That is, in a resin having a halogen element as a substituent, such as a brominated vinyl ester, the halogen element is a high refractive index substituent, so that the refractive index of the resin is considerably higher than that of the glass fiber fabric. And, in the invention of Patent Document 2, it has been found that in order to match the refractive index of the resin contained in the state of being impregnated into the glass fiber fabric with that of the glass fiber fabric, it is necessary to mix it with another component having a lower refractive index and a lower bromine concentration than the glass fiber fabric. In fact, in the examples of Patent Document 2, the refractive index is adjusted to match that of the glass fiber fabric by diluting the brominated vinyl ester with styrene, neopentyl glycol, etc., but the bromine concentration is low. Therefore, the present inventors have found that the content of the brominated vinyl ester in the sheet of Patent Document 2 is limited, the low heat generation property of the brominated vinyl ester cannot be fully utilized, and when the resin weight is increased, the weight of the glass fiber fabric must be increased at the same time, and it is still insufficient to improve the transparency of the sheet and reduce the total heat generation at the same time.

[0012] Therefore, the present inventors have further studied and found that, since Patent Document 2 requires the use of brominated vinyl ester as a resin to be impregnated into glass fiber fabric, it is necessary to dilute the concentration of bromine, which is a high refractive index substituent, to match the refractive index of the glass fiber fabric, and the content of brominated vinyl ester is limited.The present inventors have found that, in addition to a resin composition layer contained in a state impregnated in the glass fiber fabric, a resin composition layer contained in a state not impregnated in the glass fiber fabric is laminated separately from the resin composition layer contained in a state not impregnated in the glass fiber fabric, and a resin containing a bromine atom as a substituent, such as a brominated vinyl ester, is used as the resin composition layer contained in a state not impregnated in the glass fiber fabric, it is not necessary to dilute the resin containing a bromine atom as a substituent with another resin, and it is possible to further utilize the low heat generation property of the resin containing a bromine atom as a substituent. That is, it was found that by using a resin with a low bromine concentration (including a resin not containing bromine as described later) for the resin composition layer impregnated in the glass fiber fabric, the refractive index difference with the glass fiber fabric can be easily reduced, and by laminating a resin composition layer not impregnated in the glass fiber fabric separately from the resin composition layer impregnated in the glass fiber fabric, and using a resin with a high bromine concentration as the resin composition layer not impregnated in the glass fiber fabric, the low heat generation characteristic of the resin with a high bromine concentration can be fully utilized, and it is possible to more suitably achieve both improved transparency and low total heat generation when the resin weight is increased. The present invention is an invention that was completed based on these findings and through further investigation.

[0013] That is, the present invention provides the following aspects. Item 1. A transparent sheet comprising a plain woven glass fiber fabric and a resin, the transparent sheet comprising, in the thickness direction of the transparent sheet, a first resin layer contained in a state of being impregnated into the glass fiber fabric, and a second resin layer contained in a state of not being impregnated into the glass fiber fabric, the second resin layer having a higher bromine concentration than the first resin layer, the transparent sheet having a total light transmittance of 85% or more, and a haze of 10% or less. Item 2. The heat generated by a radiant electric heater is 50 kW / m2 on the surface of the sheet, measured according to "4.10.2 Heat Generation Test and Evaluation Method" in the "Fire Resistance Test and Evaluation Procedure Manual" (revised on March 1, 2014) of the General Incorporated Foundation Building Materials Testing Center. 2 In a heat generation test using radiant heat of 8 MJ / m 2 Item 2. The transparent sheet according to item 1, which is as follows: Item 3. The transparent sheet according to item 1 or 2, wherein the first resin layer is laminated on each of both sides of the second resin layer. Item 4. The total content of the resins contained in the first resin layer and the second resin layer is 200 g / m 2 4. The transparent sheet according to any one of items 1 to 3, wherein: Item 5. The transparent sheet according to any one of Items 1 to 4, wherein the total thickness of the first resin layer and the second resin layer is 180 μm or more. Item 6. The transparent sheet according to any one of Items 1 to 5, wherein the second resin layer contains a brominated vinyl ester resin. Item 7. The transparent sheet according to item 6, wherein the first resin layer contains tetrabromobisphenol A. Effect of the Invention

[0014] According to the transparent sheet of the present invention, the transparent sheet includes a plain woven glass fiber fabric and a resin, and includes a first resin layer impregnated in the glass fiber fabric and a second resin layer not impregnated in the glass fiber fabric in the thickness direction of the transparent sheet, and the second resin layer has a higher bromine concentration than the first resin layer, and the transparent sheet has a total light transmittance of 85% or more and a haze of 10% or less, so that when the resin weight is increased, it is possible to improve transparency and reduce the total heat generation. Therefore, if the transparent sheet is used to make a smoke-proof hanging wall, it is possible to make a thick smoke-proof hanging wall with a large resin weight while having excellent transparency and a low total heat generation. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a schematic cross-sectional view illustrating one embodiment of a transparent sheet of the present invention. [Diagram 2] FIG. 1 is a schematic cross-sectional view illustrating one embodiment of a transparent sheet of the present invention. [Diagram 3] FIG. 1 is a schematic cross-sectional view illustrating one embodiment of a transparent sheet of the present invention. [Figure 4] FIG. 1 is a schematic cross-sectional view illustrating one embodiment of a transparent sheet of the present invention. [Diagram 5] FIG. 1 is a schematic cross-sectional view illustrating one embodiment of a transparent sheet of the present invention. [Figure 6] FIG. 1 is a schematic cross-sectional view illustrating one embodiment of a transparent sheet of the present invention. [Figure 7] This is a diagram showing an overview of the test equipment used in 4.10.2 Heat generation test and evaluation method in the "Fire resistance performance test and evaluation procedure manual" (revised on March 1, 2014) of the General Incorporated Foundation Building Materials Testing Center. [Figure 8] This is a schematic diagram of the test holder and the press frame included in the test equipment used when performing the heat generation test and evaluation method in 4.10.2 of the "Fire Resistance Test and Evaluation Procedure Manual" (revised on March 1, 2014) of the General Incorporated Foundation Construction Materials Testing Center. The unit of the values ​​(dimensions) shown in Figure 8 is mm. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The transparent sheet of the present invention is a transparent sheet comprising a plain weave glass fiber fabric and a resin, and is characterized in that it comprises, in the thickness direction of the transparent sheet, a first resin layer contained in a state impregnated in the glass fiber fabric, and a second resin layer contained in a state not impregnated in the glass fiber fabric, the second resin layer having a higher bromine concentration than the first resin layer, and the transparent sheet having a total light transmittance of 85% or more and a haze of 10% or less.

[0017] For example, as shown in Figures 1 to 6, a transparent sheet 1 of the present invention comprises a glass fiber fabric 2, a first resin layer 3 contained in the glass fiber fabric 2 in an impregnated state, and a second resin layer 4 contained in the glass fiber fabric 2 in a non-impregnated state, and the bromine concentration of the second resin layer 4 is higher than the bromine concentration of the first resin layer 3.

[0018] The transparent sheet 1 of the present invention may contain at least one glass fiber fabric 2, or may contain multiple glass fiber fabrics. As shown in Figs. 1 to 6, the first resin layer 3 fills the gaps between the glass fibers constituting the glass fiber fabric 2 in the transparent sheet 1 of the present invention, and one surface side portion of the first resin layer 3 communicates with the other surface side portion through the gaps. As shown in Figs. 1, 3, 4, and 6, the transparent sheet 1 of the present invention may contain multiple first resin layers 3 that are impregnated in the glass fiber fabric 2. Although not shown in Figs. 1 to 6, multiple glass fiber fabrics 2 may be contained in one first resin layer 3.

[0019] In the transparent sheet 1 of the present invention, the second resin layer 4 that is included in the glass fiber without being impregnated therein may be, for example, one layer as shown in Figures 1 and 4, or may be multiple layers as shown in Figures 2, 3, 5, and 6. When the second resin layer 4 is multiple layers, it is preferably 2 to 5 layers, and more preferably 2 to 3 layers.

[0020] For example, the transparent sheet 1 in FIG. 1, FIG. 3, FIG. 4, and FIG. 6 has a laminated structure in which the first resin layer 3 is laminated on both sides of the second resin layer 4. The transparent sheet 1 in FIG. 2, FIG. 3, FIG. 5, and FIG. 6 has a laminated structure in which the second resin layer 4 is laminated on both sides of the first resin layer 3. Specific examples of the laminated structure of the first resin layer 3 and the second resin layer 4 in the transparent sheet 1 of the present invention include a laminated structure in which the first resin layer 3 / the second resin layer 4 / the first resin layer 3 are laminated in this order as shown in FIG. 1 and FIG. 4; a laminated structure in which the second resin layer 4 / the first resin layer 3 / the second resin layer 4 are laminated in this order as shown in FIG. 2 and FIG. 5; and a laminated structure in which the second resin layer 4 / the first resin layer 3 / the second resin layer 4 / the first resin layer 3 / the second resin layer 4 are laminated in this order as shown in FIG. 3 and FIG. 6.

[0021] In the transparent sheet 1 of the present invention, layers other than the first resin layer 3 and the second resin layer 4 may be provided. For example, as shown in Figs. 4 to 6, the transparent sheet 1 of the present invention may include a film layer 5. It is preferable that one film layer 5 is included on the outer side of each of the first resin layer 3 and the second resin layer 4. Although not shown, the transparent sheet 1 of the present invention may be provided with a cover layer that is peeled off when used as, for example, a hanging smoke barrier. Each layer constituting the transparent sheet 1 of the present invention will be described in detail below.

[0022] [Glass fiber fabric 2] In the transparent sheet 1 of the present invention, the glass fiber fabric 2 is included in a state in which it is impregnated with a first resin layer 3 described later. In the transparent sheet 1 of the present invention, the glass fiber fabric 2 contributes to improving the fire retardancy of the sheet. The refractive index of the glass fiber fabric 2 is set to be close to the refractive index of the first resin layer 3 described later, and this allows the transparent sheet 1 of the present invention to have a total light transmittance of 85% or more and a haze of 10% or less. In other words, the transparent sheet 1 of the present invention having a total light transmittance of 85% or more and a haze of 10% or less indicates that at least the refractive index of the glass fiber fabric 2 and the refractive index of the first resin layer 3 described later are sufficiently close (for example, the difference between the refractive index of the glass fiber fabric 2 and the refractive index of the first resin layer 3 is 0.02 or less).

[0023] In the transparent sheet 1 of the present invention, the glass fiber fabric 2 is composed of a plurality of glass fibers in a plain weave pattern. In the glass fiber fabric 2, the plurality of glass fibers are entangled with each other to form a single piece of cloth.

[0024] The glass material of the glass fibers constituting the glass fiber fabric 2 is not particularly limited, and for example, known glass materials can be used. Examples of glass materials include alkali-free glass (E glass), acid-resistant alkali-containing glass (C glass), high-strength, high-elasticity glass (S glass, T glass, etc.), and alkali-resistant glass (AR glass), and preferably includes highly versatile alkali-free glass (E glass). The glass fibers constituting the glass fiber fabric 2 may be made of one type of glass material, or may be a combination of two or more types of glass fibers made of different glass materials. In addition, from the viewpoint of improving transparency, it is preferable to select a glass material that is close to the refractive index of the first resin layer 3 described later.

[0025] The count of the glass fibers constituting the glass fiber fabric 2 is not limited to a specific one as long as the glass fiber fabric 2 can be formed. From the viewpoint of further improving transparency, the count of the glass fibers is preferably 20 tex or less, more preferably 3 to 6 tex, and more preferably 3 to 5 tex. The count of the glass fibers may be one type alone or two or more types may be combined. The tex count of the glass fibers corresponds to the number of grams per 1000 m.

[0026] The glass fibers constituting the glass fiber fabric 2 are preferably glass yarns in which a plurality of single fibers, which are long glass fibers, are twisted together. The number of single fibers in the glass yarn is preferably about 30 to 400, and more preferably about 40 to 120. The diameter of the single fiber in the glass yarn is preferably about 3.0 to 6.0 μm, and more preferably about 3.0 to 5.0 μm, from the viewpoint of further improving the transparency of the transparent sheet 1 while improving the flame retardancy of the transparent sheet 1. The count of the glass yarn is preferably 2 to 30 tex, more preferably 2 to 12 tex, and even more preferably 2 to 5 tex, from the viewpoint of further improving the transparency of the transparent sheet 1 while improving the flame retardancy of the transparent sheet 1.

[0027] In the transparent sheet 1, the total mass (g / m 2 ) and the total mass (g / m) of the first resin layer 3 described below. 2 , except for glass fiber fabric 2.) 2 The ratio (mass %) of the total mass of the glass fiber fabric 2 in the transparent sheet 1 to the total mass of the transparent sheet 1 (g / m2) is preferably 20 to 60 mass %, more preferably 30 to 60 mass %, from the viewpoint of further achieving both improved transparency and a low total heat generation when the resin weight in the transparent sheet is increased. In addition, the total mass (g / m2) of the transparent sheet 1 excluding the cover layer that is peeled off when used as a hanging smoke barrier (described later) is preferably 20 to 60 mass %, more preferably 30 to 60 mass %. 2 ) to the total mass (g / m 2 From the viewpoint of achieving both improved transparency and a low total calorific value, the proportion (mass %) of the glass fiber fabric 2 is preferably 5 to 50 mass %, more preferably 5 to 28 mass %, further preferably 5 to 25 mass %, and particularly preferably 8 to 19 mass %. 2 ) is 10~120(g / m 2 ) is preferable, and 10 to 60 (g / m 2 ) is more preferable, and 20 to 40 (g / m 2 ) is more preferable. In addition, the total mass (g / m 2) is 10 to 120 (g / m 2 ) from the viewpoint of improving the flame retardancy of the transparent sheet 1 and further improving the transparency of the transparent sheet 1. 2 ) is preferable, and 20 to 100 (g / m 2 ) is more preferable, and 30 to 80 (g / m 2 ) is particularly preferred.

[0028] The difference in refractive index between the glass fiber fabric 2 and the first resin layer 3 described below is preferably 0.02 or less, and more preferably 0.01 or less. The refractive index of the glass fiber fabric 2 is preferably about 1.50 to 1.58, and more preferably about 1.53 to 1.57.

[0029] The refractive index of the glass fiber fabric 2 is measured in accordance with the B method of JIS K 7142:2008. Specifically, first, the glass fibers constituting the glass fiber fabric are crushed to an extent that the Becke lines can be observed when observed with an optical microscope at a magnification of 400 times. Then, a halogen lamp with an interference filter for D line is used as a light source, and the optical microscope is used to observe and measure under conditions of a magnification of 400 times and a temperature of 23°C, and the average value of three tests is taken as the refractive index value. The refractive index of the first resin layer 3 and the second resin layer 4 is measured in accordance with the B method of JIS K 7142:2008. Specifically, the first resin layer 3 or the second resin layer 4 is crushed to an extent that the Becke lines can be observed when observed with an optical microscope at a magnification of 400 times. Then, a halogen lamp with an interference filter for D line is used as a light source, and the optical microscope is used to observe and measure under conditions of a magnification of 400 times and a temperature of 23°C, and the average value of three tests is taken as the refractive index value.

[0030] The difference in Abbe number between the glass fiber fabric 2 and the first resin layer 3 is preferably not more than 30, more preferably not more than 20, and even more preferably not more than 10. The Abbe number of the glass fiber fabric 2 is preferably 30 to 80, more preferably 40 to 70, and even more preferably 50 to 65. The Abbe numbers of the first resin layer 3 and the glass fiber fabric 2 are each measured as follows.

[0031] (Abbe number of first resin layer 3) A sheet not including the glass fiber fabric 2 is produced using the resin constituting the first resin layer 3, with a width of 8 mm, a length of 20 mm, and a thickness of 0.2±0.1 mm, and the refractive index at a wavelength of 589 nm is measured in accordance with JIS K 7142A using an Abbe refractometer manufactured by Atago Co., Ltd., NAR-2T, a contact liquid, diiodomethane, a light source, and sodium D line with a wavelength of 589 nm, at a measurement temperature of 23° C. Next, the dispersion value is measured and calculated using natural light as a light source, and the Abbe number is calculated according to the following formula (I). Abbe number = (Refractive index at wavelength 589 nm - 1) / Dispersion value (I)

[0032] (Abbe number of glass fiber fabric 2) A glass sheet 8 mm wide, 20 mm long, and 5±1 mm thick is prepared using the glass material that constitutes the glass fiber, the surface is thoroughly polished, and the refractive index at a wavelength of 589 nm is measured in accordance with JIS K 7142A method using an Abbe refractometer manufactured by Atago Co., Ltd., NAR-2T, diiodomethane as the contact liquid, and sodium D line with a wavelength of 589 nm as the light source at a measurement temperature of 23° C. Next, the dispersion value is measured and calculated using natural light as the light source, and the Abbe number is calculated according to the above formula (I).

[0033] From the viewpoint of improving the flame retardancy of the transparent sheet 1 and further improving the transparency of the transparent sheet 1, the thickness of each glass fiber fabric 2 is, for example, about 10 to 100 μm, preferably about 10 to 55 μm, and more preferably about 10 to 35 μm. When the thickness of the glass fiber fabric 2 is 10 to 35 μm, it is particularly preferable that the glass fiber fabric 2 has a glass volume fraction of 38% or more as calculated by the following formula (II). The glass fiber fabric 2 having a thickness of 10 to 35 μm and a glass volume fraction of 38% or more can be obtained, for example, by subjecting a glass fiber fabric to an opening treatment.

[0034] Glass volume ratio (%) = (A / (B×C))×100 (II) A: Mass of glass fiber fabric (g / m 2 ) B: Specific gravity of the glass material that composes the glass fiber fabric (g / m 3 ) C: Thickness of the glass fiber fabric (m)

[0035] (1st resin layer 3) In the transparent sheet 1 of the present invention, the first resin layer 3 is impregnated into the glass fiber fabric 2, and is formed by curing or solidifying a resin composition containing a resin. As described later, the second resin layer 4 is included in the glass fiber fabric without being impregnated therein. Therefore, at least when the first resin layer 3 and the second resin layer 4 are in contact with each other, the glass fiber fabric 2 is not exposed on the surface of the first resin layer 3, and the glass fiber fabric 2 is included in the first resin layer 3. As described above, the first resin layer 3 is selected and set to be close to the refractive index of the glass fiber fabric 2, which can reduce light scattering on the glass fiber surface, and can be configured to have a total light transmittance of 85% or more and a haze of 10% or less, as described later.

[0036] The first resin layer 3 may be a cured resin layer or a thermoplastic resin layer. When the first resin layer 3 is a cured resin layer, it may be a cured product (a photocured resin composition or a thermoset resin composition) obtained by applying energy such as light or heat to a resin composition containing a curable resin. When the first resin layer 3 is a thermoplastic resin layer, it may be a cured product obtained by drying and solidifying a thermoplastic resin composition.

[0037] In the transparent sheet 1 of the present invention, the bromine concentration of the second resin layer 4 described below must be higher than that of the first resin layer 3. That is, the inventors have found that if the bromine concentration in the resin impregnated in the glass fiber fabric is high, the calorific value of the resin is low, while the refractive index of the resin is higher than that of the glass fiber fabric, and the transparency of the resulting sheet is likely to be impaired. Therefore, the inventors have found that by using a resin with a lower bromine concentration for the first resin layer 3 impregnated in the glass fiber fabric, the difference in refractive index with the glass fiber fabric 2 can be easily reduced, and by laminating the second resin layer 4 not impregnated in the glass fiber fabric 2 separately from the first resin layer 3 impregnated in the glass fiber fabric, and using a resin with a higher bromine concentration for the second resin layer 4 not impregnated in the glass fiber fabric 2, the low heat generation characteristic of the resin with a higher bromine concentration can be fully utilized, and it is possible to achieve both improved transparency and low total calorific value when the resin weight is increased.

[0038] From the viewpoint of further reducing the haze of the transparent sheet 1 of the present invention, the bromine concentration in the first resin layer 3 is, for example, 30% by mass or less, preferably 26% by mass or less, more preferably 20% by mass or less, and even more preferably 16.7% by mass or less. The lower limit of the bromine concentration in the first resin layer 3 is 0% by mass. In other words, the first resin layer 3 may not contain bromine.

[0039] In the present invention, the bromine concentration is measured by EDS analysis. Specifically, as shown in Fig. 1 to Fig. 6, a cut surface in the thickness direction of a transparent sheet 1 is used as a measurement surface, and a sample having a thickness (i.e., the length in the vertical or horizontal direction of the transparent sheet 1) of 1 cm is used as a measurement sample, and a measurement is performed at one arbitrary point near the center in the thickness direction of the layer to be measured using an apparatus manufactured by JEOL Ltd. under the trade name JSM-6390A, and the value is regarded as the bromine concentration of each layer.

[0040] In the transparent sheet 1 of the present invention, the difference between the bromine concentration (% by mass) of the first resin layer 3 and the bromine concentration (% by mass) of the second resin layer 4 described below (=bromine concentration of the second resin layer 4−bromine concentration of the first resin layer 3) is, for example, 3% by mass or more. From the viewpoint of further achieving both improved transparency and a low total heat generation when the resin weight is increased, the difference is preferably 5 to 50% by mass, more preferably 10 to 40% by mass, and particularly preferably 20 to 30% by mass.

[0041] The curable resin used to form the first resin layer 3 is preferably one that can approximate the refractive index of the first resin layer 3 to that of the glass fiber fabric 2 described above, from the viewpoint of further improving the transparency of the transparent sheet 1. The curable resin is preferably one whose curable resin composition is photocurable, such as vinyl ester resin, urethane acrylate resin, fluorene acrylate resin, unsaturated polyester resin, curable acrylic resin, epoxy resin, etc. Among them, in the case of providing a film layer 5, from the viewpoint of further improving the adhesion with the film layer 5, a curable acrylic resin is more preferable, and a resin composition containing an acrylic syrup is particularly preferable. In the present invention, the acrylic syrup refers to a polymerizable liquid mixture in which a (meth)acrylic acid ester polymer such as polymethyl methacrylate (PMMA) is dissolved in an acrylic monomer such as methyl methacrylate. Among the above acrylic syrups, acrylic syrups obtained by dissolving one or more acrylic ester polymers selected from the group consisting of polymethyl methacrylate, methyl methacrylate / methyl acrylate copolymer, and methyl methacrylate / normal butyl acrylate copolymer in methyl methacrylate monomer are particularly preferred. In this way, when the first resin layer 3 is made of a cured resin composition containing the acrylic syrup, the adhesion with the film layer 5 is further improved, and therefore the transparency of the transparent sheet 1 is further improved, which is preferable.

[0042] The thermoplastic resin used to form the first resin layer 3 is preferably one that can approximate the refractive index of the first resin layer 3 to that of the glass fiber fabric 2, from the viewpoint of further improving the transparency of the transparent sheet 1. Examples of preferred thermoplastic resins include polyvinyl chloride resins, saturated polyester resins, polyolefin resins, thermoplastic acrylic resins, polycarbonate resins, polyvinyl alcohol resins, ethylene vinyl acetate copolymers, polyamide resins, and polyarylate resins. For example, when E-glass is used as the glass material of the glass fibers constituting the glass fiber fabric 2, polyvinyl chloride resins, saturated polyester resins, and thermoplastic acrylic resins are preferred from the viewpoint of further approximating the refractive index of both. The thermoplastic resin may be used alone, or two or more types having different refractive indices may be used in combination for the purpose of approximating the refractive index of the glass fibers used. In the transparent sheet 1 of the present invention, when the first resin layer 3 is a thermoplastic resin composition layer, the first resin layer 3 is preferably one that is impregnated with a thermoplastic resin composition in a sol state or dissolved in a solvent and solidified (solidified by heating or solidified by drying).

[0043] The resin composition constituting the first resin layer 3 is a resin composition that can generate heat of 50 kW / m 2 from a radiant electric heater on the surface of the sheet, as measured in accordance with "4.10.2 Heat Generation Test and Evaluation Method" in the "Fire Resistance Test and Evaluation Procedure Manual" (revised on March 1, 2014) of the General Incorporated Foundation Construction Materials Testing Center, which will be described later. 2 In a heat generation test using radiant heat of 200kW / m, the maximum heat generation rate continues for 10 seconds or more within 20 minutes of starting heating. 2From the viewpoint of not exceeding the above range, phosphorus may be contained. The form of phosphorus inclusion may be, for example, a resin composition made of a resin having a phosphorus atom introduced as a substituent among the above-mentioned resins, or a resin composition obtained by adding a known phosphorus-based flame retardant to the above-mentioned resin. Examples of the phosphorus-based flame retardant include those containing condensed phosphorus ester compounds such as non-halogen condensed phosphorus ester compounds and halogen-containing condensed phosphorus ester compounds, and from the viewpoint of refractive index adjustment, it is more preferable to contain a non-halogen condensed phosphorus ester compound. In addition, from the viewpoint of further suppressing the bleeding out of the phosphorus ester compound, it is more preferable to contain a condensed phosphorus ester compound having a molecular weight of 420 or more. Examples of non-halogen condensed phosphate ester compounds include 1,3-phenylene bis(diphenyl phosphate) [RDP, molecular weight 574.46], bisphenol A bis(diphenyl phosphate) [BDP, molecular weight 692.64], 1,3-phenylene bis(dixylenyl)phosphate [molecular weight 686.67], and bisphenol A bis((bisdimethylphenyl)phosphate) [molecular weight 804.86]. Examples of halogen-containing condensed phosphate ester compounds include 2,2-bis(chloromethyl)trimethylene bis(bis(2-chloroethyl)phosphate) [molecular weight 582.99]. These phosphate ester compounds may be used alone or in combination of two or more.

[0044] The resin composition constituting the first resin layer 3 is a resin composition that can withstand a heat generation test of 50 kW / m2 from a radiant electric heater to the surface of the sheet, as measured in accordance with "4.10.2 Heat Generation Test and Evaluation Method" in the "Fire Resistance Test and Evaluation Procedure Manual" (revised on March 1, 2014) of the General Incorporated Foundation Construction Materials Testing Center, which will be described later. 2 In a heat generation test using radiant heat of 200kW / m, the maximum heat generation rate continues for 10 seconds or more within 20 minutes of starting heating. 2From the viewpoint of preventing the occurrence of fire-hazardous cracks and holes penetrating to the rear surface for 20 minutes after the start of heating while keeping the mass of the glass fiber fabric 2 within the range of 40 g / m or less, it is preferable that the glass fiber fabric 2 contains tetrabromobisphenol A, decabromodiphenyl ether or brominated vinyl ester, and more preferably contains tetrabromobisphenol A. Specifically, when the mass of the glass fiber fabric 2 is, for example, 40 g / m 2 In the case where the glass fiber fabric 2 is lightweight as described below, if the first resin layer 3 impregnated in the glass fiber fabric 2 contains the above-mentioned phosphorus, the first resin layer may blister in the heat generation test, which may lead to deformation of the glass fiber fabric 2. On the other hand, if the first resin layer 3 contains tetrabromobisphenol A, decabromodiphenyl ether or brominated vinyl ester, the occurrence of the above-mentioned blister is suppressed, and cracks and holes penetrating to the back surface, which are harmful in terms of fire prevention, are even less likely to occur.

[0045] The resin composition constituting the first resin layer 3 may contain an inorganic flame retardant such as antimony trioxide or magnesium hydroxide.

[0046] The resin composition constituting the first resin layer 3 may further contain additives such as a curing accelerator, an ultraviolet absorber, a filler, and a photopolymerization initiator. Examples of the ultraviolet absorber include benzotriazole. Examples of the filler include calcium carbonate, silica, and talc. Examples of the photopolymerization initiator include 2,2-dimethoxy-1,2-diphenylethane-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one, 2-methyl-1-methyl-1-propan-1-one, and 2-methyl-1-methyl-1-propan-1-one. Examples of the additives include 1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone, 2,4,6,-trimethylbenzoyl-diphenyl-phosphine oxide, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide. Among them, when a curable acrylic resin is used as the first resin layer 3, 1-hydroxy-cyclohexyl-phenyl-ketone is preferred from the viewpoint of improving transparency. These additives may be used alone or in combination of two or more. When the first resin layer 3 contains an additive, the content thereof is preferably 0.1 to 5% by mass, more preferably 0.1 to 3% by mass.

[0047] In the transparent sheet 1 of the present invention, the total mass of the resin composition of the first resin layer 3 (excluding the glass fiber fabric 2) is, for example, 20 to 250 g / m 2 In order to improve the transparency and the non-combustibility of the resin when the resin weight is increased, the resin weight is preferably 20 to 200 g / m. 2 is preferably 20 to 120 g / m 2 More preferably, the range is from 20 to 80 g / m2 The thickness of each of the first resin layers 3 (including the glass fiber fabric 2) is, for example, 20 to 150 μm, and from the viewpoint of achieving both improved transparency and superior non-combustibility when the resin weight is increased, the thickness is preferably 20 to 100 μm, and more preferably 20 to 50 μm.

[0048] In the transparent sheet 1 of the present invention, the refractive index of the first resin layer 3 is preferably about 1.50 to 1.58, and more preferably about 1.53 to 1.57.

[0049] (2nd resin layer 4) In the transparent sheet 1 of the present invention, the second resin layer 4 is included in the glass fiber fabric 2 without being impregnated therein. As described above, the bromine concentration of the second resin layer 4 is higher than that of the first resin layer 3. In the transparent sheet 1 of the present invention, the first resin layer 3 included in the glass fiber fabric 2 without being impregnated therein is laminated with the second resin layer 4 included in the glass fiber fabric 2 without being impregnated therein, and a resin having a relatively high bromine concentration is used as the second resin layer 4 included in the glass fiber fabric 2 without being impregnated therein. As a result, the transparent sheet 1 of the present invention does not need to be made to approximate the refractive index of the glass fiber fabric 2 by diluting it with another resin having a low bromine concentration as in Patent Document 2, and the low heat generation characteristic of the resin having a high bromine concentration can be fully utilized.

[0050] The bromine concentration in the second resin layer 4 of the transparent sheet 1 of the present invention is, from the viewpoint of further suppressing the total heat generation while further increasing the resin weight, for example, 31% by mass or more, preferably 35% by mass. The upper limit is not particularly limited, but for example, 60% by mass or less, or 55% by mass or less.

[0051] Methods for incorporating bromine into the second resin layer 4 include, for example, a method in which the resin constituting the second resin layer 4 is a resin containing bromine atoms as a substituent, and a method in which a resin composition is prepared by adding a flame retardant containing bromine atoms to a curable resin or a thermoplastic resin.

[0052] The resin containing a bromine atom as a substituent may be a curable resin or a thermoplastic resin containing a bromine atom as a substituent. The curable resin containing a bromine atom as a substituent may be, for example, a brominated epoxy resin, a brominated vinyl ester resin, a brominated unsaturated polyester resin, etc. In addition, the thermoplastic resin containing a bromine atom as a substituent may be, for example, a brominated polycarbonate resin, a brominated polyurethane resin, a brominated polyester resin, etc.

[0053] Examples of the flame retardant containing a bromine atom include decabromodiphenyl, tetrabromobisphenol A (TBBA) and its derivatives, bis(pentabromophenyl)ethane, 1,2-bis(2,4,6-tribromophenoxy)ethane, brominated polystyrene, hexabromocyclododecane, hexabromobenzene, pentabromobenzyl acrylate, pentabromobenzyl acrylate, decabromodiphenyl oxide, octabromodiphenyl oxide, tetrabromodiphenyl oxide, and other phenyl oxide-based flame retardants. Examples of the resin containing the flame retardant include a resin containing a bromine atom as a substituent, and the curable resin or thermoplastic resin exemplified for the first resin layer 3.

[0054] In the transparent sheet 1 of the present invention, the total mass of the second resin layer 4 is, for example, 100 to 600 g / m 2 and 180 to 500 g / m 2 The thickness of each of the second resin layers 4 is, for example, from 80 to 600 μm, and preferably from 100 to 400 μm.

[0055] In the transparent sheet 1 of the present invention, the refractive index of the second resin layer 4 is not particularly limited, and may be, for example, 1.570 to 1.650, more preferably 1.572 to 1.620, and further preferably 1.580 to 1.620. The difference between the refractive index of the glass fiber fabric 2 and the refractive index of the second resin layer 4 may be greater than 0.01, and may be greater than 0.02.

[0056] From the viewpoint of achieving both improved transparency and low total heat generation of the transparent sheet 1 of the present invention and further increasing the resin weight of the transparent sheet 1 to effectively increase the mechanical strength, the total content of the resins constituting the first resin layer 3 and the second resin layer 4 (the total of the first resin layer 3 (excluding the mass of the glass fiber fabric 2) and the second resin layer 4 contained in the transparent sheet 1) is preferably 200 g / m 2 More preferably, 240 g / m 2 More preferably, 270 g / m 2 The upper limit of the total content is, for example, 600 g / m 2 The following are included:

[0057] From the same viewpoint, the total thickness of the first resin layer 3 and the second resin layer 4 (the total thickness of all the first resin layers 3 and second resin layers 4 included in the transparent sheet 1) is preferably 180 μm or more, more preferably 200 μm or more, and further preferably 240 μm or more. The upper limit of the total thickness is, for example, 500 μm or less, or 450 μm or less.

[0058] (Film layer 5) In the transparent sheet 1 of the present invention, the film layer 5 is laminated on the first resin layer 3 or the second resin layer 4 as necessary, and serves to further improve the initial tear strength of the transparent sheet 1. It is preferable that one film layer 5 is included on the outer side of each of the first resin layer 3 and the second resin layer 4.

[0059] The material constituting the film layer 5 is not particularly limited. Examples of the material include polyester resin, polycarbonate resin, polyolefin resin, fluororesin, acrylic resin, and polyamide resin. On the other hand, the film layer 5 preferably contains a thermoplastic resin other than polyvinyl chloride resin. Examples of the thermoplastic resin other than polyvinyl chloride resin include those that can be made into a film even with a small amount of plasticizer, and a biaxially stretched film containing an amorphous thermoplastic resin other than polyvinyl chloride resin is preferred. Examples of the thermoplastic resin other than polyvinyl chloride resin include polyester resin, polycarbonate resin, fluororesin, acrylic resin, and polyamide resin, and at least one of these may be included. The film layer 5 may also not contain polyvinyl chloride resin. From the viewpoint of further improving the initial tear strength of the transparent sheet 1, the film layer 5 may have an Elmendorf tear propagation resistance of 1 N / mm or more in both the vertical and horizontal directions, preferably 3 to 20 N / mm, and more preferably 5 to 15 N / mm. Among them, from the viewpoint of achieving a better balance between chemical resistance (including alkaline detergent resistance when used as a smoke barrier), improved initial tear strength, and transparency, it is preferable that the film layer 5 contains a polyester resin. Examples of the polyester resin include polyethylene terephthalate (PET) and polyethylene naphthalate (PEN). The Elmendorf tear propagation resistance means the tear propagation resistance (N / mm) obtained by measuring the tear strength (N) based on JIS K7128-2·1998 using an Elmendorf tearing machine manufactured by Toyo Seiki Seisakusho Co., Ltd. and dividing the measured value by the film thickness. The tear strength is the average value of the test results of 20 samples in each of the vertical and horizontal directions. If the film layer 5 is made of a resin composition containing PVDF and an acrylic resin (PMMA, etc.), it will have excellent weather resistance and excellent adhesion to the first resin layer 3 and the second resin layer 4, and will be suitable as a membrane material.

[0060] In the transparent sheet of the present invention, the film to be used for the film layer 5 is preferably excellent in transparency and smoothness. As the transparency of the film to be used for the film layer 5, for example, the total light transmittance (JIS K 7105:1981) is preferably 90% or more, more preferably 91 to 98%, and for example, the haze (JIS K 7105:1981) is preferably 1.5% or less, more preferably 0.3 to 1.0%.

[0061] (Antistatic layer containing metal or metal compound) The transparent sheet 1 of the present invention may be provided with an antistatic layer containing a metal or a metal compound so as to become the outermost layer when used as, for example, a smoke barrier.

[0062] In the antistatic layer containing a metal or a metal compound, examples of the metal element contained include Ag, Ni, Cu, Sn, Sb, Al, In, Ti, etc., and examples of the metal element have a standard electrode potential of less than 0 eV when it is a simple metal. Examples of the metal compound include metal oxides (antimony pentoxide, tin oxide, zinc oxide, indium oxide, antimony-doped indium oxide, tin-doped indium oxide, silver oxide, etc.). In addition, the antistatic layer may not contain fine particles made of barium sulfate, calcium carbonate, aluminum oxide, magnesium silicate, glass, etc. Examples of the form in which the metal or metal compound is contained include a metal or metal compound thin film formed by vapor deposition, sputtering, plating, etc., or a layer in which metal or metal compound fine particles are dispersed in a fixing resin. Examples of the shape of the metal or metal compound fine particles include granular, flake, and needle (fibrous). The average particle diameter of the metal or metal compound fine particles is, for example, the average particle diameter determined by the BET method (specific surface area (m2) measured by nitrogen gas adsorption method). 2 By making the specific surface area diameter (calculated as the average particle diameter from the specific surface area diameter (particle diameter) calculated by a conventional method from the specific surface area diameter (particle diameter) / g) 100 nm or less, which is equal to or less than the wavelength of visible light, and preferably 1 to 100 nm, the transparency of the transparent sheet 1 can be more easily maintained.

[0063] When the antistatic layer containing a metal or a metal compound contains metal or metal compound fine particles, it is preferable that the layer contains an adhesive resin that fixes the metal or metal compound fine particles to the substrate. That is, it is preferable that the antistatic layer is a layer containing an adhesive resin and metal or metal compound fine particles dispersed in the adhesive resin. Examples of the adhesive resin include polyurethane resin, polyester resin, acrylic resin, polyether resin, cellulose resin, polyvinyl alcohol resin, epoxy resin, polyvinylpyrrolidone, polystyrene resin, polyethylene glycol, and pentaerythritol, and polyurethane resin, polyester resin, and acrylic resin are particularly preferable. Examples of the acrylic resin include modified acrylic resin (urethane modified, polyester modified, polycarbonate modified, fluorine modified, etc.). The mass of the antistatic layer is, for example, 0.1 to 10 g / m per layer. 2 and 0.1 to 5 g / m 2 is preferably 0.1 to 3 g / m 2 More preferably, the range is 0.1 to 1 g / m 2 is particularly preferred. The thickness of the antistatic layer is, for example, 0.01 to 3 μm per layer, and preferably 0.05 to 1 μm. The mass ratio of the fixing resin to the metal or metal compound fine particles in the antistatic layer (mass of the fixing resin (g / m 2 ): Mass of metal or metal compound particles (g / m 2 ) is preferably 10:1 to 1:1, more preferably 8:1 to 2:1, and particularly preferably 4:1 to 2:1. When an antistatic layer containing a metal or a metal compound is provided, the surface smoothness may be, for example, a surface roughness Ra of 1 to 200 nm. The total mass (g / m 2 ) of the mass of metal and metal compound particles (g / m 2 The proportion of ) is 50 to 10 mass %, and preferably 30 to 20 mass %.

[0064] (Removable cover layer that is peeled off when used) The transparent sheet 1 of the present invention may further have a peelable cover layer laminated thereon, as necessary, on the outer side of the first resin layer 3, the second resin layer 4, or the film layer 5 (on the outer side of the antistatic layer 6 when the antistatic layer 6 is provided on the outer side of the first resin layer 3, the second resin layer 4, or the film layer 5). The peelable cover layer may be suitably provided on the outermost surface of the transparent sheet 1 of the present invention. This makes it easier to prevent, for example, when the transparent sheet 1 of the present invention is used as a hanging smoke barrier, from causing scratches or the like on the transparent sheet 1 during construction, which would reduce transparency and aesthetics.

[0065] As the peelable cover layer peeled off during use, for example, a polyethylene film, a polytetrafluoroethylene film, a polypropylene film, a polyester film, etc. can be used. Among them, if a light-transmitting protective film is used as the peelable cover layer peeled off during use, for example, when the resin composition forming the first resin layer 3 or the second resin layer 4 is a photocurable curable resin composition, it is preferable in that it is easy to prevent the surface of the layer that becomes the outermost layer during use from being scratched or the like, and the transparency and aesthetics from being reduced, even in the process of curing the curable resin composition. The light transmittance is not particularly limited as long as it transmits light that cures the photocurable resin, but examples of the light transmittance include those that transmit light with a wavelength of 100 to 400 nm and those that transmit light with a wavelength of 250 to 400 nm. As the light transmittance of the cover layer, for example, the average transmittance between the measurement wavelengths of 250 to 400 nm measured with a UV transmittance meter (manufactured by Shimadzu Corporation under the trade name UV3150) is preferably 40% or more, more preferably 50% or more, and particularly preferably 60% or more.

[0066] In addition, the peelable cover layer that is peeled off when used is not particularly limited in transparency and smoothness because it is peeled off when used, such as a smoke barrier, etc. For example, from the viewpoint of cost, the total light transmittance is about 80 to 95% (JIS K 7105: 1981) and the haze is about 2 to 10% (JIS K 7105: 1981).

[0067] (Properties of Transparent Sheet 1) The transparent sheet 1 of the present invention has a total light transmittance of 85% or more (if a peelable cover layer that is peeled off during use is included, the total light transmittance after peeling off the cover layer) and a haze of 10% or less (if a peelable cover layer that is peeled off during use is included, the haze after peeling off the cover layer). As described above, the total light transmittance of the transparent sheet 1 of the present invention is 85% or more and the haze is 10% or less indicates that at least the refractive index of the glass fiber fabric 2 and the refractive index of the first resin layer 3 are sufficiently close to each other (for example, the difference between the refractive index of the glass fiber fabric 2 and the refractive index of the first resin layer 3 is 0.02 or less). The total light transmittance is preferably 90% or more. The haze is preferably 5% or less, more preferably 3% or less, and particularly preferably 1% or less. The total light transmittance of the transparent sheet 1 is a value obtained by measurement in accordance with JIS K7361-1 1997, and the haze is a value obtained by measurement in accordance with JIS K 7136:2000.

[0068] The thickness of the transparent sheet 1 of the present invention is, for example, 200 to 700 μm, preferably 250 to 600 μm, after peeling off the peelable cover layer that is peeled off during use (i.e., the thickness excluding the peelable cover layer that is peeled off during use). The mass of the transparent sheet 1 of the present invention is, for example, 200 to 800 g / m, after peeling off the peelable cover layer that is peeled off during use (i.e., the mass excluding the peelable cover layer that is peeled off during use). 2 and 400 to 750 g / m 2 In addition, the total mass of the resin in the transparent sheet 1 after peeling off the peelable cover layer that is peeled off during use (for example, when the transparent sheet 1 has the laminated structure shown in FIG. 4, the total mass of the resin in the first resin layer 3, the second resin layer 4, and the film layer 5) is, for example, 300 to 700 g / m 2 390 to 700 g / m 2 is preferably 450 to 650 g / m 2 are more preferred.

[0069] The transparent sheet 1 of the present invention has a surface heat resistance of 50 kW / m2 from a radiant electric heater, as measured in accordance with "4.10.2 Heat Generation Test and Evaluation Method" in the "Fire Resistance Performance Test and Evaluation Procedure Manual" (revised version as of March 1, 2014) of the General Incorporated Foundation Construction Materials Testing Center, after peeling off a peelable cover layer that is peeled off during use. 2 In a heat generation test using radiant heat of 8 MJ / m 2 Furthermore, the transparent sheet 1 of the present invention, after peeling off the peelable cover layer that is peeled off during use, has a maximum heat generation rate of 200 kW / m2 or less continuously for 10 seconds or more after the start of heating in the heat generation test. 2 It is preferable not to exceed .

[0070] In the present invention, the heat generated by a radiant electric heater is 50 kW / m on the surface of the sheet, as measured in accordance with "4.10.2 Heat Generation Test and Evaluation Method" in the "Fire Resistance Test and Evaluation Procedure Manual" (revised on March 1, 2014) of the General Incorporated Foundation Construction Materials Testing Center. 2 The total heat generation amount (MJ / m) in the heat generation test in which radiant heat is irradiated 2 ) and the maximum heat generation rate after heating starts is 200kW / m 2 Specifically, the time (S) exceeding this limit is performed in accordance with the test specimen, test equipment, and test conditions described below.

[0071] [Test specimen] (1) The number of test specimens (sheets) shall be three. (2) The shape and dimensions of the test specimen shall be a square with each side measuring 99 mm ± 1 mm. [Test equipment] (1) A schematic diagram of the test equipment used is shown in Figure 7. The test equipment consists of a cone-shaped radiant electric heater, an ignition plug, a radiant heat shield, a test specimen holder, a gas concentration analyzer, an exhaust system capable of measuring gas flow rate, and a heat flow meter. (2) Radiant electric heater: 50 kW / m 2 The radiant heat must be able to be irradiated uniformly and stably onto the surface of the test piece. (3) The radiant heat shield shall be capable of protecting the test specimen from radiant heat before the test begins. (4) A schematic diagram of the test holder and presser frame included in the test equipment is shown in Figure 8. The specimen holder shall be made of stainless steel and have an outer dimension of 106 mm ± 1 mm on each side, a depth of 25 mm ± 1 mm, and a thickness of 2.15 mm ± 0.25 mm, with a square opening of 94.0 mm ± 0.5 mm on each side at the center of the upper part. The presser frame shall be made of stainless steel and have an inner dimension of 111 mm ± 1 mm on each side, and a depth of 54 mm ± 1 mm. (5) The exhaust system shall be equipped with a centrifugal exhaust fan, hood, ventilation opening, exhaust duct, orifice plate flow meter, etc. that function effectively at the test temperature. The distance between the bottom end of the hood and the surface of the test specimen shall be 210 mm ± 50 mm. In that state, the exhaust device of the exhaust system shall have a flow rate of 0.024 m when converted to standard temperature and standard pressure. 3 / s or more. For the purpose of measuring the exhaust flow rate, an orifice with an inner diameter of 57 mm ± 3 mm is provided between the hood and the duct. For the purpose of sampling the exhaust gas, a ring sampler with 12 holes with a diameter of 2.2 mm ± 0.1 mm is attached 685 mm ± 15 mm from the hood with the holes facing in the opposite direction to the flow. In addition, the exhaust gas temperature is measured at the centre of the exhaust duct 100 mm ± 5 mm upstream from the orifice. The orifice is placed in a position that does not affect the flow measurement. (6) The gas analyzer shall be capable of continuously and accurately measuring the concentrations of oxygen, carbon monoxide, and carbon dioxide in the exhaust gas. (7) The ignition plug shall be capable of receiving power from a 10kV transformer or induction coil system, etc. The distance between the spark electrodes shall be 3mm±0.5mm, and the electrodes shall be located, in principle, 13mm±2mm on the central axis of the test specimen. (8) The heat flow meter is 100kW / m 2 ±10kW / m 2 The heat sensing part of the heat flow meter is a circle with a diameter of 12.5 mm, and the surface emissivity is 0.95 ± 0.05. [Test conditions] (1) The test time shall be 20 minutes from the time when radiant heat is applied to the surface of the test specimen and an electric spark is generated at the same time. However, the measurement may be terminated when the combustion clearly does not continue. (2) The sides and back of the specimen are wrapped in aluminum foil with a thickness of 0.025 mm or more and 0.04 mm or less, placed in a press frame, and then coated with inorganic fiber (nominal thickness 13 mm, density 65 kg / m 3 ) and then pressed into the specimen holder. (3) During the test, a radiant electric heater applied 50 kW / m to the surface of the test specimen. 2 It emits radiant heat. (4) Exhaust gas flow rate of 0.024 m 3 / s±0.002m 3 Adjust to / s. (5) Until the start of the test, a radiant heat shield is used to protect the test specimen from radiant heat. (6) Before moving the radiation heat shield, set the spark plug in the designated position. [measurement] (1) Measure the concentrations of oxygen, carbon monoxide, and carbon dioxide at intervals of not more than 5 seconds. (2) The heat generation rate per unit area (kW / m) was calculated using the following method: 2 ) and then calculate the total heat generation per unit area (MJ / m 2 ) is calculated by accumulating the heat release rate from the start to the end of heating.

[0072] The heat release rate (q) is calculated according to the following formula:

[0073]

number

[0074] Where: V 298 =C(Δp Te) 1 / 2 / 350 (: Duct flow rate at 25℃) E = 17.2 × 10 3 kJ / m 3 X 0 O2 : Average oxygen concentration measured over 1 minute X O2 : Actual measured oxygen concentration The heat generation rate per unit area (q") is: q”=q / As Where: As: Initial exposed area of ​​the specimen (0.0088 m 2 ). C (orifice coefficient) is the value that indicates the heat generation rate of the exhaust gas under the specified exhaust flow rate. b = Oxygen concentration when methane is burned at a flow rate equivalent to 5kW ± 0.5kW (X O2 ) and differential pressure (△p) using the following formula. C=q b / (△hc / ro×1.10)(Te / △p) 1 / 2 (1.105-1.5X O2 ) / (0.2095-X O2 ) Where: q b : Heat release rate of methane supplied △hc / ro: 12.54×10 for methane 3 kJ / kg Te: Gas temperature in the exhaust duct (measured near the two-way pitot tube)

[0075] (Method of manufacturing the transparent sheet 1 of the present invention) The method for producing the transparent sheet 1 of the present invention is not particularly limited, but may include, for example, a first step of preparing an intermediate body containing a glass fiber fabric 2 in an impregnated state with a first resin layer 3, and a second step of laminating a second resin layer 4 on the intermediate body. An example of the laminate structure shown in FIG. 1 will be described below.

[0076] The first step will be described taking the case where the resin constituting the first resin layer 3 is a curable resin as an example. In the first step, first, a glass fiber fabric 2 and an uncured curable resin composition to be the first resin layer 3 are prepared. The uncured curable resin composition is applied to a process film (e.g., a PET film, etc.), the glass fiber fabric 2 is placed on the applied uncured curable resin composition, and the glass fiber fabric 2 is impregnated with the uncured curable resin composition. Next, another process film (e.g., a PET film, etc.) is placed on the uncured curable resin composition impregnated in the glass fiber fabric 2, and pressure is applied from above the process film B with a roller to adjust the mass of the first resin layer 3. Then, the uncured curable resin composition to be the first resin layer 3 is irradiated with light using a black light fluorescent lamp through the processing PET film B to cure the curable resin composition, forming the first resin layer 3, and then one of the processing films (process film A for convenience in this example) is peeled off to obtain an intermediate having a laminated structure of the processing film B / the first resin layer 3 impregnated in the glass fiber fabric 2. Two intermediates are prepared. At this time, when the transparent sheet 1 includes a film layer 5, the film layer 5 can be used instead of the processing film B included in the intermediate. In addition, when the transparent sheet 1 includes, for example, a film layer 5 and a peelable cover layer that is peeled off when used, the film layer 5 and the peelable cover layer that is peeled off when used are laminated in advance to form a laminated film, and the laminated film can be used instead of the processing film B included in the intermediate so that the cover layer is on the surface side.

[0077] The second step will be described by taking the case where the resin constituting the second resin layer 4 is a curable resin. In the second step, an uncured curable resin to be the second resin layer 4 is prepared, and the uncured curable resin is applied to the first resin layer 3 side of the intermediate obtained in the first step. Next, the other intermediate obtained is placed on the uncured curable resin to be the second resin layer 4 so that the first resin layer 3 side is the uncured curable resin to be the second resin layer 4 side, and the mass of the second resin layer 4 is adjusted by pressing the other intermediate with a roller. Thereafter, the uncured curable resin composition to be the second resin layer 4 is irradiated with light using a black light fluorescent lamp through the other intermediate to cure the curable resin composition, and the second resin layer 4 is formed and laminated. Then, by peeling off the process films B on both surfaces of the second resin layer 4, the transparent sheet 1 of the present invention can be obtained, which has a laminated structure of the first resin layer 3 contained in a state impregnated in the glass fiber fabric 2 / the second resin layer 4 contained in a state not impregnated in the glass fiber fabric 2 / the first resin layer 3 contained in a state impregnated in the glass fiber fabric 2. When the film layer 5 is included or when a cover layer that can be peeled off during use is included, the uncured curable resin composition that is to be the second resin layer 4 is cured to form the second resin layer 4, and then the film layer 5 and the cover layer that can be peeled off during use are not peeled off to form the transparent sheet 1.

[0078] (Uses of the transparent sheet 1 of the present invention) The transparent sheet 1 of the present invention can be used as a hanging smokeproof wall that is hung down from the ceiling of a building. Examples of the hanging smokeproof wall include known ones using a transparent sheet 1 made of glass fiber fabric and resin, such as a hanging smokeproof wall that includes a mounting rail arranged on the ceiling surface of a building, a transparent sheet 1 that is hung with its upper end held by the mounting rail, and a pair of end mullions arranged on both sides of the transparent sheet 1, and the transparent sheet 1 and the end mullions are joined so as to be freely separated. Examples of the hanging smokeproof wall include a hanging wall in which the transparent sheet 1 is stretched between two pairs of mullions, such as a hanging smokeproof wall that does not have a blind on the lower side of the transparent sheet 1 when it is hung down from the ceiling. In addition, when the transparency is increased, it can be used as a substitute for glass, so it can also be used in other applications in which glass is used, such as partitions, partitions, smokeproof sheets, and smokeproof curtains (for example, those used in factories, etc.). EXAMPLES

[0079] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to the examples.

[0080] The resin composition constituting the first resin layer 3 to be impregnated into the above-mentioned glass fiber fabric 2 was a mixture of acrylic syrup (manufactured by Ryoko Corporation, product name "Acrysirup XD8005" (refractive index 1.550)), a non-halogen condensed phosphate ester compound RDP (manufactured by ADEKA Corporation, product name "ADEKA STAB PFR"), and a photopolymerization initiator (manufactured by IGM, Omnirad 184) (mass ratio (acrylic syrup:non-halogen condensed phosphate ester compound:photopolymerization initiator) = 70:30:3) in Examples 1 to 6, and a mixture of acrylic syrup (manufactured by Ryoko Corporation, product name "XY1087" (refractive index 1.520), "XY1088" (refractive index 1.540), tetrabromobisphenol A (TBBA, product name "Framecut 120G" manufactured by Tosoh Corporation), and a photopolymerization initiator (manufactured by IGM, Omnirad 184) in Examples 7 to 10. A mixture of brominated vinyl ester resin (manufactured by Japan U-PICA Corporation under the trade name Neopol 8197) and photopolymerization initiator (manufactured by IGM under the trade name Omnirad 184) (mass ratio (acrylic syrup XY1087:acrylic syrup XY1088:TBBA:photopolymerization initiator) = 34:42:24:3) was used as the resin composition constituting the second resin layer 4, which is not impregnated in the glass fiber fabric 2, and which was used in the composition shown in Table 1. The amount of the photopolymerization initiator was 3 parts by mass per 100 parts by mass of the brominated vinyl ester resin. As the film layer 5, two types of commercially available biaxially stretched polyester films manufactured by Toyobo Co., Ltd. (trade name "Cosmoshine (registered trademark) A4300", thickness 38 μm, mass 53 g / m) were used. 2 , total light transmittance (JIS K 7105:1981) 93%, haze (JIS K 7105:1981) 0.9%), (product name "Cosmoshine (registered trademark) A4300", thickness 50 μm, mass 70 g / m 2, total light transmittance (JIS K 7105:1981) 93%, haze (JIS K 7105:1981) 0.9%, and a commercially available film containing PVDF and acrylic resin (a PVDF and PMMA alloy in which Sheet A has a PVDF content of 80% by mass and a PMMA content of 20% by mass, and Sheet B has a PVDF content of 20% by mass and a PMMA content of 80% by mass, joined together (manufactured by Denka Company Ltd., product name "Denka DX Film DX-14S50", thickness 50 μm, mass 68 g / m 2 The total light transmittance (JIS K 7105:1981) was 92%, and the haze (JIS K 7105:1981) was 5%. A polypropylene film (thickness 40 μm, mass 36 g / m) was used as a peelable cover layer that is peeled off during use. 2 ), one side of which was coated with an acrylic acid ester-based adhesive that could be peeled off and adhered to the film layer 5, and a PET film (thickness 50 μm, total light transmittance 93%, haze 4% (JIS K 7105:1981)). The PET film was also used as a process film, which will be described later.

[0081] <Example 1> (Preparation of fiberglass fabric) The warp and weft yarns were made of Unitika Glass Fiber Co., Ltd.'s product name "ECC1200 1 / 0 1.0Z" (average filament diameter 4.5 μm, average number of filaments 100, twist number 1.0Z, yarn count 4.2 tex), and woven with an air jet loom to obtain a plain weave glass fiber fabric with a warp density of 90 / 25 mm and a weft density of 90 / 25 mm. Next, the spinning bundling agent and weaving bundling agent attached to the obtained glass fiber fabric were removed by heating at 400°C for 30 hours. After that, the surface treatment agent, a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) Chisso Corporation) was adjusted to a concentration of 15 g / L, and the fabric was squeezed with a padder roll, followed by drying and curing at 120°C for 1 minute. The glass fiber fabric was then subjected to a water flow process at a pressure of 1.5 MPa, with the tension of the glass fiber fabric being 100 N / m in the warp direction, and a width-widening process was carried out once to obtain a glass fiber fabric 2. The obtained glass fiber fabric had a warp density of 90 threads / 25 mm, a weft density of 90 threads / 25 mm, a thickness of 27 μm, and a mass of 30 g / m 2 , the refractive index was 1.561.

[0082] (Lamination of antistatic layer to film layer 5) An antistatic layer was laminated on one side of Cosmoshine (registered trademark) A4300 (thickness 38 μm) as the film layer 5. The antistatic layer was provided by coating and drying an antistatic agent prepared by mixing and dispersing tin oxide fine particles (average particle diameter 20 nm) in a polyester resin as an adhesive resin such that the mass ratio of the adhesive resin to the tin oxide fine particles (adhesive resin:tin oxide fine particles) was 75:25 on one side of Cosmoshine (registered trademark) A4300 (thickness 38 μm) as the film layer 5. The mass of the provided antistatic layer was 0.5 g / m 2 , and the thickness was 0.4 μm.

[0083] (Lamination of a peelable protective film to be peeled off during use onto film layer 5 (antistatic layer side) layer) The above-mentioned Cosmoshine (registered trademark) A4300 having an antistatic layer on one side thereof as film layer 5 was laminated with a polypropylene film having an acrylic ester adhesive on one side thereof as a peelable cover layer to be peeled off when used, so that the adhesive was on the antistatic layer side, and dried to obtain a laminate X having a laminate structure of Cosmoshine (registered trademark) A4300 having a peelable protective film to be peeled off when used / acrylic ester adhesive / antistatic layer / film layer 5. Two sheets of the laminate X were prepared.

[0084] (Formation of the first resin layer 3, and lamination of the laminate A including the film layer 5 onto the first resin layer 3) A curable resin composition made of the acrylic syrup shown in Table 1 was applied as the first resin layer 3 to the COSMOSHINE (registered trademark) A4300 side of one sheet of the obtained laminate X (i.e., the side opposite to the peelable cover layer to be peeled off during use). Next, the obtained glass fiber fabric 2 was placed on the curable resin composition to be the first resin layer 3, and left to stand for 1 minute to impregnate the gaps in the glass fiber fabric 2 with the curable resin composition made of the acrylic syrup. Next, the PET film used as the process film was placed on the curable resin composition made of the acrylic syrup, and the PET film was rolled with a roller until the mass of the first resin layer 3 was 30 g / m. 2 Thereafter, the curable resin composition made of acrylic syrup that was to be the first resin layer 3 through the PET film in the above process was irradiated with light (light irradiation conditions: cumulative light amount 200 mJ / cm 2 ) using a black light fluorescent lamp (manufactured by Toshiba Corporation, product name FL15BLB). 2) to cure the curable resin composition to form a first resin layer 3, and then the laminated processed PET film was peeled off to obtain a laminate Y having a laminated structure of a peelable cover layer that is peeled off when used / an acrylic acid ester-based adhesive that is peelable together with the cover layer / an antistatic layer / a film layer 5 (Cosmoshine (registered trademark) A4300) / a first resin layer 3 contained in a state of being impregnated in a glass fiber fabric 2. In the obtained laminate Y, the first resin layer 3 (a cured product of a resin composition) made of an acrylic syrup was impregnated into the gaps between the glass fibers of the glass fiber fabric 2 without exposing the glass fibers. Two sheets of the laminate Y were prepared.

[0085] (Lamination of the second resin layer 4 included in the glass fiber fabric 2 without being impregnated therein) A brominated vinyl ester resin composition shown in Table 1 was applied to the first resin layer 3 side of one sheet of the obtained laminate Y, the second resin layer 4 being contained in a state of not being impregnated in the glass fiber fabric 2. Next, the other one of the obtained laminates Y was placed on top of the brominated vinyl ester resin composition so that the first resin layer 3 side of the laminate Y faced the brominated vinyl ester resin composition side, and the second resin layer 4 made of the brominated vinyl ester resin composition was rolled with a roller from above the other laminate Y until the mass of the second resin layer 4 was 183 g / m 2 Thereafter, the brominated vinyl ester resin composition to be the second resin layer 4 was irradiated with light (light irradiation conditions: cumulative light amount 200 mJ / cm 2 ) using a black light fluorescent lamp (manufactured by Toshiba Corporation, product name FL15BLB) through the other laminate Y. 2) to harden the brominated vinyl ester resin composition to form a second resin layer 4, and a transparent sheet 1 of the present invention having a laminated structure of a peelable cover layer peeled off when used / acrylic ester-based adhesive peelable together with the cover layer / antistatic layer / film layer 5 (Cosmoshine (registered trademark) A4300) / first resin layer 3 contained in a state impregnated in the glass fiber fabric 2 / second resin layer 4 contained in a state not impregnated in the glass fiber fabric 2 / first resin layer 3 contained in a state impregnated in the glass fiber fabric 2 / film layer 5 (Cosmoshine (registered trademark) A4300) / antistatic layer / acrylic ester-based adhesive peelable together with the cover layer / peelable cover layer peeled off when used was obtained. The bromine concentration, total light transmittance, haze, total heat generation, and 200 kW over time of the transparent sheet described later were evaluated by peeling off the peelable cover layer peeled off when using the obtained transparent sheet 1 and the acrylic ester-based adhesive peelable together with the cover layer.

[0086] <Example 2> In the lamination of the second resin layer 4 that is not impregnated in the glass fiber fabric 2 in Example 1, the mass of the second resin layer 4 made of the brominated vinyl ester resin composition was 233 g / m 2 from above the other laminate Y with a roller. 2 The same procedure as in Example 1 was carried out, except that the pressure was applied so that the thickness was 100 mm, and the transparent sheet 1 of the present invention was obtained, which has a laminated structure of a peelable cover layer peeled off when used / acrylic ester-based adhesive peelable together with the cover layer / antistatic layer / film layer 5 (Cosmoshine (registered trademark) A4300) / first resin layer 3 contained in a state impregnated in the glass fiber fabric 2 / second resin layer 4 contained in a state not impregnated in the glass fiber fabric 2 / first resin layer 3 contained in a state impregnated in the glass fiber fabric 2 / film layer 5 (Cosmoshine (registered trademark) A4300) / antistatic layer / acrylic ester-based adhesive peelable together with the cover layer / peelable cover layer peeled off when used. The evaluation of the bromine concentration, total light transmittance, haze, total heat generation, and 200 kW over time of the transparent sheet described later was performed by peeling off the peelable cover layer peeled off when using the obtained transparent sheet 1 and the acrylic ester-based adhesive peelable together with the cover layer.

[0087] <Example 3> In the lamination of the second resin layer 4 that is not impregnated in the glass fiber fabric 2 in Example 1, the mass of the second resin layer 4 made of the brominated vinyl ester resin composition was 322 g / m 2 from above the other laminate Y with a roller. 2 The same procedure as in Example 1 was carried out, except that the pressure was applied so that the thickness was 100 mm, and the transparent sheet 1 of the present invention was obtained, which has a laminated structure of a peelable cover layer peeled off when used / acrylic ester-based adhesive peelable together with the cover layer / antistatic layer / film layer 5 (Cosmoshine (registered trademark) A4300) / first resin layer 3 contained in a state impregnated in the glass fiber fabric 2 / second resin layer 4 contained in a state not impregnated in the glass fiber fabric 2 / first resin layer 3 contained in a state impregnated in the glass fiber fabric 2 / film layer 5 (Cosmoshine (registered trademark) A4300) / antistatic layer / acrylic ester-based adhesive peelable together with the cover layer / peelable cover layer peeled off when used. The evaluation of the bromine concentration, total light transmittance, haze, total heat generation, and 200 kW over time of the transparent sheet described later was performed by peeling off the peelable cover layer peeled off when using the obtained transparent sheet 1 and the acrylic ester-based adhesive peelable together with the cover layer.

[0088] <Example 4> In the lamination of the second resin layer 4 that is not impregnated in the glass fiber fabric 2 in Example 1, the mass of the second resin layer 4 made of the brominated vinyl ester resin composition was 476 g / m 2 from above the other laminate Y with a roller. 2The same procedure as in Example 1 was carried out, except that the pressure was applied so that the thickness was 100 mm, and the transparent sheet 1 of the present invention was obtained, which has a laminated structure of a peelable cover layer peeled off when used / acrylic ester-based adhesive peelable together with the cover layer / antistatic layer / film layer 5 (Cosmoshine (registered trademark) A4300) / first resin layer 3 contained in a state impregnated in the glass fiber fabric 2 / second resin layer 4 contained in a state not impregnated in the glass fiber fabric 2 / first resin layer 3 contained in a state impregnated in the glass fiber fabric 2 / film layer 5 (Cosmoshine (registered trademark) A4300) / antistatic layer / acrylic ester-based adhesive peelable together with the cover layer / peelable cover layer peeled off when used. The evaluation of the bromine concentration, total light transmittance, haze, total heat generation, and 200 kW over time of the transparent sheet described later was performed by peeling off the peelable cover layer peeled off when using the obtained transparent sheet 1 and the acrylic ester-based adhesive peelable together with the cover layer.

[0089] <Example 5> (Preparation of fiberglass fabric) The warp and weft yarns were made of Unitika Glass Fiber Co., Ltd.'s product name "ECE225 1 / 0 1.0Z" (average filament diameter 7.0 μm, average number of filaments 200, twist number 1.0Z, yarn count 22.5 tex), and woven with an air jet loom to obtain a plain weave glass fiber fabric with a warp density of 60 / 25 mm and a weft density of 57 / 25 mm. Next, the spinning bundling agent and weaving bundling agent attached to the obtained glass fiber fabric were removed by heating at 400°C for 30 hours. Thereafter, a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) Chisso Corporation) as a surface treatment agent was adjusted to a concentration of 15 g / L, and the fabric was squeezed with a padder roll, followed by drying and curing at 120°C for 1 minute to obtain glass fiber fabric 2. The obtained glass fiber fabric had a warp density of 60 threads / 25 mm, a weft density of 57 threads / 25 mm, a thickness of 90 μm, and a mass of 105 g / m 2 , the refractive index was 1.561.

[0090] (Formation of first resin layer 3 and lamination of film layer 5 onto first resin layer 3) A curable resin composition made of the acrylic syrup shown in Table 1 was applied to the PET film used as the above-mentioned process film to form the first resin layer 3. Next, the above-obtained glass fiber fabric 2 was placed on the curable resin composition made of the first resin layer 3, and left to stand for 1 minute to impregnate the gaps in the glass fiber fabric 2 with the curable resin composition made of the acrylic syrup. Next, another sheet of the PET film used as the above-mentioned process film was placed on the curable resin composition made of the acrylic syrup, and the PET film was rolled with a roller until the mass of the first resin layer 3 became 105 g / m2. 2 Thereafter, the curable resin composition made of acrylic syrup that was to be the first resin layer 3 through the PET film in the above process was irradiated with light (light irradiation conditions: cumulative light amount 200 mJ / cm 2 ) using a black light fluorescent lamp (manufactured by Toshiba Corporation, product name FL15BLB). 2 ) to cure the curable resin composition to form a first resin layer 3, and then one of the PET films to be used as a processing film that had been laminated as above was peeled off to obtain a laminate Z having a laminate structure of a PET film to be used as a processing film and a first resin layer 3 contained in an impregnated state in a glass fiber fabric 2. In the obtained laminate Z, the first resin layer 3 (cured product of the resin composition) made of acrylic syrup was impregnated into the gaps between the glass fibers of the glass fiber fabric 2 without exposing the glass fibers. Two sheets of the laminate Z were prepared.

[0091] (Lamination of the second resin layer 4 included in the glass fiber fabric 2 without being impregnated therein) A brominated vinyl ester resin composition shown in Table 1 was applied to the first resin layer 3 side of one of the obtained laminates Z, which was contained in a state of being impregnated in the glass fiber fabric 2, as the second resin layer 4, which was contained in a state of not being impregnated in the glass fiber fabric 2. Next, the other of the obtained laminates Z was placed on top of the brominated vinyl ester resin composition, so that the first resin layer 3 side of the laminate Z faced the brominated vinyl ester resin composition side, and the second resin layer 4 made of the brominated vinyl ester resin composition was rolled from above the other laminate Z with a roller until the mass of the second resin layer 4 was 184 g / m 2Thereafter, the brominated vinyl ester resin composition to be the second resin layer 4 was irradiated with light (light irradiation conditions: cumulative light amount 200 mJ / cm 2 ) using a black light fluorescent lamp (manufactured by Toshiba Corporation, product name FL15BLB) through the other laminate Z. 2 ) to harden the brominated vinyl ester resin composition to form a second resin layer 4, and the PET films serving as process films on both sides were peeled off to obtain a laminate consisting of a first resin layer 3 contained in a state impregnated in the glass fiber fabric 2 / a second resin layer 4 contained in a state not impregnated in the glass fiber fabric 2 / a first resin layer 3 contained in a state impregnated in the glass fiber fabric 2. The obtained laminate was sandwiched between two sheets containing the above-mentioned PVDF and acrylic resin to serve as film layers 5, with the surface of each of the two sheets bonding to the laminate facing sheet B (i.e., the acrylic resin-rich surface), and pressed in a heating press at a temperature of 160°C and a pressure of 10 kgf / cm. 2 The laminate was pressed under conditions of 100° C., 100° C., and 5 minutes for a time period of 100 min to bond the laminate to a sheet containing PVDF and acrylic resin, thereby obtaining a transparent sheet 1 of the present invention having a laminate structure of film layer 5 (sheet containing PVDF and acrylic resin) / first resin layer 3 contained in a state impregnated in glass fiber fabric 2 / second resin layer 4 contained in a state not impregnated in glass fiber fabric 2 / first resin layer 3 contained in a state impregnated in glass fiber fabric 2 / film layer 5 (sheet containing PVDF and acrylic resin). Evaluations of bromine concentration, total light transmittance, haze, total heat generation, and 200 kW excess time of the transparent sheet described below were performed using the transparent sheet obtained above.

[0092] <Example 6> (Preparation of fiberglass fabric) The warp and weft yarns were made of Unitika Glass Fiber Co., Ltd.'s product name "ECBC2250 1 / 0 0.5Z" (average filament diameter 4.0 μm, average number of filaments 66, twist number 0.5Z, yarn count 2.3 tex), and woven with an air jet loom to obtain a plain weave glass fiber fabric with a warp density of 95 / 25 mm and a weft density of 95 / 25 mm. Next, the spinning bundling agent and weaving bundling agent attached to the obtained glass fiber fabric were removed by heating at 400°C for 30 hours. Thereafter, a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) Chisso Corporation) as a surface treatment agent was adjusted to a concentration of 15 g / L, and the fabric was squeezed with a padder roll, followed by drying and curing at 120°C for 1 minute to obtain glass fiber fabric 2. The obtained glass fiber fabric had a warp density of 95 threads / 25 mm, a weft density of 95 threads / 25 mm, a thickness of 15 μm, and a mass of 17 g / m 2 , the refractive index was 1.561.

[0093] (Lamination of antistatic layer to film layer 5) An antistatic layer was laminated on one side of Cosmoshine (registered trademark) A4300 (thickness 50 μm) as the film layer 5. The antistatic layer was provided by coating and drying an antistatic agent prepared by mixing and dispersing tin oxide fine particles (average particle diameter 20 nm) in a polyester resin as an adhesive resin such that the mass ratio of the adhesive resin to the tin oxide fine particles (adhesive resin:tin oxide fine particles) was 75:25 on one side of Cosmoshine (registered trademark) A4300 (thickness 50 μm) as the film layer 5. The mass of the provided antistatic layer was 0.5 g / m 2 , and the thickness was 0.4 μm.

[0094] (Lamination of a peelable protective film onto film layer 5 (antistatic layer side) which is peeled off during use) The above-mentioned Cosmoshine (registered trademark) A4300 having an antistatic layer on one side thereof as film layer 5 was laminated with a polypropylene film having an acrylic ester adhesive on one side thereof as a peelable cover layer to be peeled off when used, so that the adhesive was on the antistatic layer side, and dried to obtain a laminate X having a laminate structure of Cosmoshine (registered trademark) A4300 having a peelable protective film to be peeled off when used / acrylic ester adhesive / antistatic layer / film layer 5. Two sheets of the laminate X were prepared.

[0095] (Formation of the first resin layer 3, and lamination of the laminate A including the film layer 5 onto the first resin layer 3) A curable resin composition made of the acrylic syrup shown in Table 1 was applied as the first resin layer 3 to the COSMOSHINE (registered trademark) A4300 side (i.e., the side opposite to the peelable cover layer to be peeled off during use) of one sheet of the obtained laminate X. Next, the obtained glass fiber fabric 2 was placed on the curable resin composition to be the first resin layer 3, and left to stand for 1 minute to impregnate the gaps in the glass fiber fabric 2 with the curable resin composition made of the acrylic syrup. Next, the PET film used as the process film described above was placed on the curable resin composition made of the acrylic syrup, and the PET film was rolled with a roller until the mass of the first resin layer 3 became 25 g / m. 2 Thereafter, the curable resin composition made of acrylic syrup that was to be the first resin layer 3 through the PET film in the above process was irradiated with light (light irradiation conditions: cumulative light amount 200 mJ / cm 2 ) using a black light fluorescent lamp (manufactured by Toshiba Corporation, product name FL15BLB). 2) to cure the curable resin composition to form a first resin layer 3, and then the laminated processed PET film was peeled off to obtain a laminate Y having a laminated structure of a peelable cover layer that is peeled off when used / an acrylic acid ester-based adhesive that is peelable together with the cover layer / an antistatic layer / a film layer 5 (Cosmoshine (registered trademark) A4300) / a first resin layer 3 contained in a state of being impregnated in a glass fiber fabric 2. In the obtained laminate Y, the first resin layer 3 (a cured product of a resin composition) made of an acrylic syrup was impregnated into the gaps between the glass fibers of the glass fiber fabric 2 without exposing the glass fibers. Two sheets of the laminate Y were prepared.

[0096] (Lamination of the second resin layer 4 included in the glass fiber fabric 2 without being impregnated therein) A brominated vinyl ester resin composition shown in Table 1 was applied to the first resin layer 3 side of one sheet of the obtained laminate Y, the second resin layer 4 being contained in a state of not being impregnated in the glass fiber fabric 2. Next, the other one of the obtained laminates Y was placed on top of the brominated vinyl ester resin composition so that the first resin layer 3 side of the laminate Y faced the brominated vinyl ester resin composition side, and the second resin layer 4 made of the brominated vinyl ester resin composition was rolled with a roller from above the other laminate Y until the mass of the second resin layer 4 was 387 g / m 2 Thereafter, the brominated vinyl ester resin composition to be the second resin layer 4 was irradiated with light (light irradiation conditions: cumulative light amount 200 mJ / cm 2 ) using a black light fluorescent lamp (manufactured by Toshiba Corporation, product name FL15BLB) through the other laminate Y. 2) to harden the brominated vinyl ester resin composition to form a second resin layer 4, and a transparent sheet 1 of the present invention having a laminated structure of a peelable cover layer peeled off when used / acrylic ester-based adhesive peelable together with the cover layer / antistatic layer / film layer 5 (Cosmoshine (registered trademark) A4300) / first resin layer 3 contained in a state impregnated in the glass fiber fabric 2 / second resin layer 4 contained in a state not impregnated in the glass fiber fabric 2 / first resin layer 3 contained in a state impregnated in the glass fiber fabric 2 / film layer 5 (Cosmoshine (registered trademark) A4300) / antistatic layer / acrylic ester-based adhesive peelable together with the cover layer / peelable cover layer peeled off when used was obtained. The bromine concentration, total light transmittance, haze, total heat generation, and 200 kW over time of the transparent sheet described later were evaluated by peeling off the peelable cover layer peeled off when using the obtained transparent sheet 1 and the acrylic ester-based adhesive peelable together with the cover layer.

[0097] <Example 7> (Preparation of fiberglass fabric) The warp and weft yarns were made of Unitika Glass Fiber Co., Ltd.'s product name "ECC1200 1 / 0 1.0Z" (average filament diameter 4.5 μm, average number of filaments 100, twist number 1.0Z, yarn count 4.2 tex), and woven with an air jet loom to obtain a plain weave glass fiber fabric with a warp density of 90 / 25 mm and a weft density of 90 / 25 mm. Next, the spinning bundling agent and weaving bundling agent attached to the obtained glass fiber fabric were removed by heating at 400°C for 30 hours. After that, the surface treatment agent, a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) Chisso Corporation) was adjusted to a concentration of 15 g / L, and the fabric was squeezed with a padder roll, followed by drying and curing at 120°C for 1 minute. The glass fiber fabric was then subjected to a water flow process at a pressure of 1.5 MPa, with the tension of the glass fiber fabric being 100 N / m in the warp direction, and a width-widening process was carried out once to obtain a glass fiber fabric 2. The obtained glass fiber fabric had a warp density of 90 threads / 25 mm, a weft density of 90 threads / 25 mm, a thickness of 27 μm, and a mass of 30 g / m 2 , the refractive index was 1.561.

[0098] (Lamination of antistatic layer to film layer 5) An antistatic layer was laminated on one side of Cosmoshine (registered trademark) A4300 (thickness 50 μm) as the film layer 5. The antistatic layer was provided by coating and drying an antistatic agent prepared by mixing and dispersing tin oxide fine particles (average particle diameter 20 nm) in a polyester resin as an adhesive resin such that the mass ratio of the adhesive resin to the tin oxide fine particles (adhesive resin:tin oxide fine particles) was 75:25 on one side of Cosmoshine (registered trademark) A4300 (thickness 50 μm) as the film layer 5. The mass of the provided antistatic layer was 0.5 g / m 2 , and the thickness was 0.4 μm.

[0099] (Lamination of a peelable protective film onto film layer 5 (antistatic layer side) which is peeled off during use) The above-mentioned Cosmoshine (registered trademark) A4300 having an antistatic layer on one side thereof as film layer 5 was laminated with a polypropylene film having an acrylic ester adhesive on one side thereof as a peelable cover layer to be peeled off when used, so that the adhesive was on the antistatic layer side, and dried to obtain a laminate X having a laminate structure of Cosmoshine (registered trademark) A4300 having a peelable protective film to be peeled off when used / acrylic ester adhesive / antistatic layer / film layer 5. Two sheets of the laminate X were prepared.

[0100] (Formation of the first resin layer 3, and lamination of the laminate A including the film layer 5 onto the first resin layer 3) A curable resin composition made of the acrylic syrup shown in Table 1 was applied as the first resin layer 3 to the COSMOSHINE (registered trademark) A4300 side (i.e., the side opposite to the peelable cover layer to be peeled off during use) of one sheet of the obtained laminate X. Next, the obtained glass fiber fabric 2 was placed on the curable resin composition to be the first resin layer 3, and left to stand for 1 minute to impregnate the gaps in the glass fiber fabric 2 with the curable resin composition made of the acrylic syrup. Next, the PET film used as the process film described above was placed on the curable resin composition made of the acrylic syrup, and the PET film was rolled with a roller until the mass of the first resin layer 3 became 25 g / m. 2 Thereafter, the curable resin composition made of acrylic syrup that was to be the first resin layer 3 through the PET film in the above process was irradiated with light (light irradiation conditions: cumulative light amount 200 mJ / cm 2 ) using a black light fluorescent lamp (manufactured by Toshiba Corporation, product name FL15BLB). 2 ) to cure the curable resin composition to form a first resin layer 3, and then the laminated processed PET film was peeled off to obtain a laminate Y having a laminated structure of a peelable cover layer that is peeled off when used / an acrylic acid ester-based adhesive that is peelable together with the cover layer / an antistatic layer / a film layer 5 (Cosmoshine (registered trademark) A4300) / a first resin layer 3 contained in a state of being impregnated in a glass fiber fabric 2. In the obtained laminate Y, the first resin layer 3 (a cured product of a resin composition) made of an acrylic syrup was impregnated into the gaps between the glass fibers of the glass fiber fabric 2 without exposing the glass fibers. Two sheets of the laminate Y were prepared.

[0101] (Lamination of the second resin layer 4 included in the glass fiber fabric 2 without being impregnated therein) A brominated vinyl ester resin composition shown in Table 1 was applied to the first resin layer 3 side of one sheet of the obtained laminate Y, the second resin layer 4 being contained in a state of not being impregnated in the glass fiber fabric 2. Next, the other one of the obtained laminates Y was placed on top of the brominated vinyl ester resin composition so that the first resin layer 3 side of the laminate Y faced the brominated vinyl ester resin composition side, and the second resin layer 4 made of the brominated vinyl ester resin composition was rolled from above the other laminate Y with a roller until the mass of the second resin layer 4 was 149 g / m 2 Thereafter, the brominated vinyl ester resin composition to be the second resin layer 4 was irradiated with light (light irradiation conditions: cumulative light amount 200 mJ / cm 2 ) using a black light fluorescent lamp (manufactured by Toshiba Corporation, product name FL15BLB) through the other laminate Y. 2 ) to harden the brominated vinyl ester resin composition to form a second resin layer 4, and a transparent sheet 1 of the present invention having a laminated structure of a peelable cover layer peeled off when used / acrylic ester-based adhesive peelable together with the cover layer / antistatic layer / film layer 5 (Cosmoshine (registered trademark) A4300) / first resin layer 3 contained in a state impregnated in the glass fiber fabric 2 / second resin layer 4 contained in a state not impregnated in the glass fiber fabric 2 / first resin layer 3 contained in a state impregnated in the glass fiber fabric 2 / film layer 5 (Cosmoshine (registered trademark) A4300) / antistatic layer / acrylic ester-based adhesive peelable together with the cover layer / peelable cover layer peeled off when used was obtained. The bromine concentration, total light transmittance, haze, total heat generation, and 200 kW over time of the transparent sheet described later were evaluated by peeling off the peelable cover layer peeled off when using the obtained transparent sheet 1 and the acrylic ester-based adhesive peelable together with the cover layer.

[0102] <Example 8> (Preparation of fiberglass fabric) The warp and weft yarns were made of Unitika Glass Fiber Co., Ltd.'s product name "ECC1200 1 / 0 1.0Z" (average filament diameter 4.5 μm, average number of filaments 100, twist number 1.0Z, yarn count 4.2 tex), and woven with an air jet loom to obtain a plain weave glass fiber fabric with a warp density of 90 / 25 mm and a weft density of 90 / 25 mm. Next, the spinning bundling agent and weaving bundling agent attached to the obtained glass fiber fabric were removed by heating at 400°C for 30 hours. After that, the surface treatment agent, a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) Chisso Corporation) was adjusted to a concentration of 15 g / L, and the fabric was squeezed with a padder roll, followed by drying and curing at 120°C for 1 minute. The glass fiber fabric was then subjected to a water flow process at a pressure of 1.5 MPa, with the tension of the glass fiber fabric being 100 N / m in the warp direction, and a width-widening process was carried out once to obtain a glass fiber fabric 2. The obtained glass fiber fabric had a warp density of 90 threads / 25 mm, a weft density of 90 threads / 25 mm, a thickness of 27 μm, and a mass of 30 g / m 2 , the refractive index was 1.561.

[0103] (Lamination of antistatic layer to film layer 5) An antistatic layer was laminated on one side of Cosmoshine (registered trademark) A4300 (thickness 50 μm) as the film layer 5. The antistatic layer was provided by coating and drying an antistatic agent prepared by mixing and dispersing tin oxide fine particles (average particle diameter 20 nm) in a polyester resin as an adhesive resin such that the mass ratio of the adhesive resin to the tin oxide fine particles (adhesive resin:tin oxide fine particles) was 75:25 on one side of Cosmoshine (registered trademark) A4300 (thickness 50 μm) as the film layer 5. The mass of the provided antistatic layer was 0.5 g / m 2 , and the thickness was 0.4 μm.

[0104] (Lamination of a peelable protective film onto film layer 5 (antistatic layer side) which is peeled off during use) The above-mentioned Cosmoshine (registered trademark) A4300 having an antistatic layer on one side thereof as film layer 5 was laminated with a polypropylene film having an acrylic ester adhesive on one side thereof as a peelable cover layer to be peeled off when used, so that the adhesive was on the antistatic layer side, and dried to obtain a laminate X having a laminate structure of Cosmoshine (registered trademark) A4300 having a peelable protective film to be peeled off when used / acrylic ester adhesive / antistatic layer / film layer 5. Two sheets of the laminate X were prepared.

[0105] (Formation of the first resin layer 3, and lamination of the laminate A including the film layer 5 onto the first resin layer 3) A curable resin composition made of the acrylic syrup shown in Table 1 was applied as the first resin layer 3 to the COSMOSHINE (registered trademark) A4300 side (i.e., the side opposite to the peelable cover layer to be peeled off during use) of one sheet of the obtained laminate X. Next, the obtained glass fiber fabric 2 was placed on the curable resin composition to be the first resin layer 3, and left to stand for 1 minute to impregnate the gaps in the glass fiber fabric 2 with the curable resin composition made of the acrylic syrup. Next, the PET film used as the process film described above was placed on the curable resin composition made of the acrylic syrup, and the PET film was rolled with a roller until the mass of the first resin layer 3 became 25 g / m. 2 Thereafter, the curable resin composition made of acrylic syrup that was to be the first resin layer 3 through the PET film in the above process was irradiated with light (light irradiation conditions: cumulative light amount 200 mJ / cm 2 ) using a black light fluorescent lamp (manufactured by Toshiba Corporation, product name FL15BLB). 2) to cure the curable resin composition to form a first resin layer 3, and then the laminated processed PET film was peeled off to obtain a laminate Y having a laminated structure of a peelable cover layer that is peeled off when used / an acrylic acid ester-based adhesive that is peelable together with the cover layer / an antistatic layer / a film layer 5 (Cosmoshine (registered trademark) A4300) / a first resin layer 3 contained in a state of being impregnated in a glass fiber fabric 2. In the obtained laminate Y, the first resin layer 3 (a cured product of a resin composition) made of an acrylic syrup was impregnated into the gaps between the glass fibers of the glass fiber fabric 2 without exposing the glass fibers. Two sheets of the laminate Y were prepared.

[0106] (Lamination of the second resin layer 4 included in the glass fiber fabric 2 without being impregnated therein) A brominated vinyl ester resin composition shown in Table 1 was applied to the first resin layer 3 side of one sheet of the obtained laminate Y, the second resin layer 4 being contained in a state of not being impregnated in the glass fiber fabric 2. Next, the other one of the obtained laminates Y was placed on top of the brominated vinyl ester resin composition so that the first resin layer 3 side of the laminate Y faced the brominated vinyl ester resin composition side, and the second resin layer 4 made of the brominated vinyl ester resin composition was rolled from above the other laminate Y with a roller until the mass of the second resin layer 4 was 189 g / m 2 Thereafter, the brominated vinyl ester resin composition to be the second resin layer 4 was irradiated with light (light irradiation conditions: cumulative light amount 200 mJ / cm 2 ) using a black light fluorescent lamp (manufactured by Toshiba Corporation, product name FL15BLB) through the other laminate Y. 2) to harden the brominated vinyl ester resin composition to form a second resin layer 4, and a transparent sheet 1 of the present invention having a laminated structure of a peelable cover layer peeled off when used / acrylic ester-based adhesive peelable together with the cover layer / antistatic layer / film layer 5 (Cosmoshine (registered trademark) A4300) / first resin layer 3 contained in a state impregnated in the glass fiber fabric 2 / second resin layer 4 contained in a state not impregnated in the glass fiber fabric 2 / first resin layer 3 contained in a state impregnated in the glass fiber fabric 2 / film layer 5 (Cosmoshine (registered trademark) A4300) / antistatic layer / acrylic ester-based adhesive peelable together with the cover layer / peelable cover layer peeled off when used was obtained. The bromine concentration, total light transmittance, haze, total heat generation, and 200 kW over time of the transparent sheet described later were evaluated by peeling off the peelable cover layer peeled off when using the obtained transparent sheet 1 and the acrylic ester-based adhesive peelable together with the cover layer.

[0107] <Example 9> (Preparation of fiberglass fabric) The warp and weft yarns were made of Unitika Glass Fiber Co., Ltd.'s product name "ECC1200 1 / 0 1.0Z" (average filament diameter 4.5 μm, average number of filaments 100, twist number 1.0Z, yarn count 4.2 tex), and woven with an air jet loom to obtain a plain weave glass fiber fabric with a warp density of 90 / 25 mm and a weft density of 90 / 25 mm. Next, the spinning bundling agent and weaving bundling agent attached to the obtained glass fiber fabric were removed by heating at 400°C for 30 hours. After that, the surface treatment agent, a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) Chisso Corporation) was adjusted to a concentration of 15 g / L, and the fabric was squeezed with a padder roll, followed by drying and curing at 120°C for 1 minute. The glass fiber fabric was then subjected to a water flow process at a pressure of 1.5 MPa, with the tension of the glass fiber fabric being 100 N / m in the warp direction, and a width-widening process was carried out once to obtain a glass fiber fabric 2. The obtained glass fiber fabric had a warp density of 90 threads / 25 mm, a weft density of 90 threads / 25 mm, a thickness of 27 μm, and a mass of 30 g / m 2 , the refractive index was 1.561.

[0108] (Lamination of antistatic layer to film layer 5) An antistatic layer was laminated on one side of Cosmoshine (registered trademark) A4300 (thickness 50 μm) as the film layer 5. The antistatic layer was provided by coating and drying an antistatic agent prepared by mixing and dispersing tin oxide fine particles (average particle diameter 20 nm) in a polyester resin as an adhesive resin such that the mass ratio of the adhesive resin to the tin oxide fine particles (adhesive resin:tin oxide fine particles) was 75:25 on one side of Cosmoshine (registered trademark) A4300 (thickness 50 μm) as the film layer 5. The mass of the provided antistatic layer was 0.5 g / m 2 , and the thickness was 0.4 μm.

[0109] (Lamination of a peelable protective film onto film layer 5 (antistatic layer side) which is peeled off during use) The above-mentioned Cosmoshine (registered trademark) A4300 having an antistatic layer on one side thereof as film layer 5 was laminated with a polypropylene film having an acrylic ester adhesive on one side thereof as a peelable cover layer to be peeled off when used, so that the adhesive was on the antistatic layer side, and dried to obtain a laminate X having a laminate structure of Cosmoshine (registered trademark) A4300 having a peelable protective film to be peeled off when used / acrylic ester adhesive / antistatic layer / film layer 5. Two sheets of the laminate X were prepared.

[0110] (Formation of the first resin layer 3, and lamination of the laminate A including the film layer 5 onto the first resin layer 3) A curable resin composition made of the acrylic syrup shown in Table 1 was applied as the first resin layer 3 to the COSMOSHINE (registered trademark) A4300 side (i.e., the side opposite to the peelable cover layer to be peeled off during use) of one sheet of the obtained laminate X. Next, the obtained glass fiber fabric 2 was placed on the curable resin composition to be the first resin layer 3, and left to stand for 1 minute to impregnate the gaps in the glass fiber fabric 2 with the curable resin composition made of the acrylic syrup. Next, the PET film used as the process film described above was placed on the curable resin composition made of the acrylic syrup, and the PET film was rolled with a roller until the mass of the first resin layer 3 became 25 g / m. 2 Thereafter, the curable resin composition made of acrylic syrup that was to be the first resin layer 3 through the PET film in the above process was irradiated with light (light irradiation conditions: cumulative light amount 200 mJ / cm 2 ) using a black light fluorescent lamp (manufactured by Toshiba Corporation, product name FL15BLB). 2 ) to cure the curable resin composition to form a first resin layer 3, and then the laminated processed PET film was peeled off to obtain a laminate Y having a laminated structure of a peelable cover layer that is peeled off when used / an acrylic acid ester-based adhesive that is peelable together with the cover layer / an antistatic layer / a film layer 5 (Cosmoshine (registered trademark) A4300) / a first resin layer 3 contained in a state of being impregnated in a glass fiber fabric 2. In the obtained laminate Y, the first resin layer 3 (a cured product of a resin composition) made of an acrylic syrup was impregnated into the gaps between the glass fibers of the glass fiber fabric 2 without exposing the glass fibers. Two sheets of the laminate Y were prepared.

[0111] (Lamination of the second resin layer 4 included in the glass fiber fabric 2 without being impregnated therein) A brominated vinyl ester resin composition shown in Table 1 was applied to the first resin layer 3 side of one sheet of the obtained laminate Y, the second resin layer 4 being contained in a state of not being impregnated in the glass fiber fabric 2. Next, the other one of the obtained laminates Y was placed on top of the brominated vinyl ester resin composition so that the first resin layer 3 side of the laminate Y faced the brominated vinyl ester resin composition side, and the second resin layer 4 made of the brominated vinyl ester resin composition was rolled with a roller from above the other laminate Y until the mass of the second resin layer 4 was 229 g / m 2 Thereafter, the brominated vinyl ester resin composition to be the second resin layer 4 was irradiated with light (light irradiation conditions: cumulative light amount 200 mJ / cm 2 ) using a black light fluorescent lamp (manufactured by Toshiba Corporation, product name FL15BLB) through the other laminate Y. 2 ) to harden the brominated vinyl ester resin composition to form a second resin layer 4, and a transparent sheet 1 of the present invention having a laminated structure of a peelable cover layer peeled off when used / acrylic ester-based adhesive peelable together with the cover layer / antistatic layer / film layer 5 (Cosmoshine (registered trademark) A4300) / first resin layer 3 contained in a state impregnated in the glass fiber fabric 2 / second resin layer 4 contained in a state not impregnated in the glass fiber fabric 2 / first resin layer 3 contained in a state impregnated in the glass fiber fabric 2 / film layer 5 (Cosmoshine (registered trademark) A4300) / antistatic layer / acrylic ester-based adhesive peelable together with the cover layer / peelable cover layer peeled off when used was obtained. The bromine concentration, total light transmittance, haze, total heat generation, and 200 kW over time of the transparent sheet described later were evaluated by peeling off the peelable cover layer peeled off when using the obtained transparent sheet 1 and the acrylic ester-based adhesive peelable together with the cover layer.

[0112] <Example 10> (Preparation of fiberglass fabric) The warp and weft yarns were made of Unitika Glass Fiber Co., Ltd.'s product name "ECC1200 1 / 0 1.0Z" (average filament diameter 4.5 μm, average number of filaments 100, twist number 1.0Z, yarn count 4.2 tex), and woven with an air jet loom to obtain a plain weave glass fiber fabric with a warp density of 90 / 25 mm and a weft density of 90 / 25 mm. Next, the spinning bundling agent and weaving bundling agent attached to the obtained glass fiber fabric were removed by heating at 400°C for 30 hours. After that, the surface treatment agent, a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) Chisso Corporation) was adjusted to a concentration of 15 g / L, and the fabric was squeezed with a padder roll, followed by drying and curing at 120°C for 1 minute. The glass fiber fabric was then subjected to a water flow process at a pressure of 1.5 MPa, with the tension of the glass fiber fabric being 100 N / m in the warp direction, and a width-widening process was carried out once to obtain a glass fiber fabric 2. The obtained glass fiber fabric had a warp density of 90 threads / 25 mm, a weft density of 90 threads / 25 mm, a thickness of 27 μm, and a mass of 30 g / m 2 , the refractive index was 1.561.

[0113] (Lamination of antistatic layer to film layer 5) An antistatic layer was laminated on one side of Cosmoshine (registered trademark) A4300 (thickness 50 μm) as the film layer 5. The antistatic layer was provided by coating and drying an antistatic agent prepared by mixing and dispersing tin oxide fine particles (average particle diameter 20 nm) in a polyester resin as an adhesive resin such that the mass ratio of the adhesive resin to the tin oxide fine particles (adhesive resin:tin oxide fine particles) was 75:25 on one side of Cosmoshine (registered trademark) A4300 (thickness 50 μm) as the film layer 5. The mass of the provided antistatic layer was 0.5 g / m 2 , and the thickness was 0.4 μm.

[0114] (Lamination of a peelable protective film onto film layer 5 (antistatic layer side) which is peeled off during use) The above-mentioned Cosmoshine (registered trademark) A4300 having an antistatic layer on one side thereof as film layer 5 was laminated with a polypropylene film having an acrylic ester adhesive on one side thereof as a peelable cover layer to be peeled off when used, so that the adhesive was on the antistatic layer side, and dried to obtain a laminate X having a laminate structure of Cosmoshine (registered trademark) A4300 having a peelable protective film to be peeled off when used / acrylic ester adhesive / antistatic layer / film layer 5. Two sheets of the laminate X were prepared.

[0115] (Formation of the first resin layer 3, and lamination of the laminate A including the film layer 5 onto the first resin layer 3) A curable resin composition made of the acrylic syrup shown in Table 1 was applied as the first resin layer 3 to the COSMOSHINE (registered trademark) A4300 side (i.e., the side opposite to the peelable cover layer to be peeled off during use) of one sheet of the obtained laminate X. Next, the obtained glass fiber fabric 2 was placed on the curable resin composition to be the first resin layer 3, and left to stand for 1 minute to impregnate the gaps in the glass fiber fabric 2 with the curable resin composition made of the acrylic syrup. Next, the PET film used as the process film described above was placed on the curable resin composition made of the acrylic syrup, and the PET film was rolled with a roller until the mass of the first resin layer 3 became 25 g / m. 2 Thereafter, the curable resin composition made of acrylic syrup that was to be the first resin layer 3 through the PET film in the above process was irradiated with light (light irradiation conditions: cumulative light amount 200 mJ / cm 2 ) using a black light fluorescent lamp (manufactured by Toshiba Corporation, product name FL15BLB). 2) to cure the curable resin composition to form a first resin layer 3, and then the laminated processed PET film was peeled off to obtain a laminate Y having a laminated structure of a peelable cover layer that is peeled off when used / an acrylic acid ester-based adhesive that is peelable together with the cover layer / an antistatic layer / a film layer 5 (Cosmoshine (registered trademark) A4300) / a first resin layer 3 contained in a state of being impregnated in a glass fiber fabric 2. In the obtained laminate Y, the first resin layer 3 (a cured product of a resin composition) made of an acrylic syrup was impregnated into the gaps between the glass fibers of the glass fiber fabric 2 without exposing the glass fibers. Two sheets of the laminate Y were prepared.

[0116] (Lamination of the second resin layer 4 included in the glass fiber fabric 2 without being impregnated therein) A brominated vinyl ester resin composition shown in Table 1 was applied to the first resin layer 3 side of one sheet of the obtained laminate Y, the second resin layer 4 being contained in a state of not being impregnated in the glass fiber fabric 2. Next, the other one of the obtained laminates Y was placed on top of the brominated vinyl ester resin composition so that the first resin layer 3 side of the laminate Y faced the brominated vinyl ester resin composition side, and the second resin layer 4 made of the brominated vinyl ester resin composition was rolled from above the other laminate Y with a roller until the mass of the second resin layer 4 was 269 g / m 2 Thereafter, the brominated vinyl ester resin composition to be the second resin layer 4 was irradiated with light (light irradiation conditions: cumulative light amount 200 mJ / cm 2 ) using a black light fluorescent lamp (manufactured by Toshiba Corporation, product name FL15BLB) through the other laminate Y. 2) to harden the brominated vinyl ester resin composition to form a second resin layer 4, and a transparent sheet 1 of the present invention having a laminated structure of a peelable cover layer peeled off when used / acrylic ester-based adhesive peelable together with the cover layer / antistatic layer / film layer 5 (Cosmoshine (registered trademark) A4300) / first resin layer 3 contained in a state impregnated in the glass fiber fabric 2 / second resin layer 4 contained in a state not impregnated in the glass fiber fabric 2 / first resin layer 3 contained in a state impregnated in the glass fiber fabric 2 / film layer 5 (Cosmoshine (registered trademark) A4300) / antistatic layer / acrylic ester-based adhesive peelable together with the cover layer / peelable cover layer peeled off when used was obtained. The bromine concentration, total light transmittance, haze, total heat generation, and 200 kW over time of the transparent sheet described later were evaluated by peeling off the peelable cover layer peeled off when using the obtained transparent sheet 1 and the acrylic ester-based adhesive peelable together with the cover layer.

[0117] In the examples, the weave density of the glass fiber fabric was measured and calculated according to JIS R 3420 2013 7.9. The thickness of the glass fiber fabric was measured and calculated according to JIS R 3420 2013 7.10.1A. The mass of the glass fiber fabric was measured and calculated according to JIS R 3420 2013 7.2. The refractive indexes of the glass fiber fabric 2, the first resin layer 3, and the second resin layer 4 were measured and calculated by the above-mentioned method. The Abbe numbers of the glass fiber fabric 2 and the first resin layer 3 were measured and calculated by the above-mentioned method. The following evaluations were performed after the transparent sheet 1 was produced and left indoors for one week.

[0118] The bromine concentration was measured and calculated by the method described above.

[0119] The total light transmittance and haze of the transparent sheet 1 after peeling off the peelable cover layer that is peeled off during use are measured according to "4.10.2 Heat generation test and evaluation method" in the "Fire resistance performance test and evaluation business method manual" (revised version on March 1, 2014) of the General Incorporated Foundation Building Materials Testing Center, and the ...2 The total heat generation amount (MJ / m) in the heat generation test in which radiant heat is irradiated 2 ) and heat generation rate of 200kW / m 2 The time (S) exceeding this limit was measured and calculated using the method described above. The presence or absence of through holes was determined for the sheet 20 minutes after the start of heating in accordance with the above "4.10.2 Heat generation test - evaluation method."

[0120] The evaluation results are shown in Tables 1 and 2.

[0121] [Table 1]

[0122] [Table 2]

[0123] As is clear from Tables 1 and 2, the transparent sheets of Examples 1 to 10 were transparent sheets comprising a plain weave glass fiber fabric and a resin, and included, in the thickness direction of the transparent sheet, a first resin layer contained in a state of being impregnated into the glass fiber fabric, and a second resin layer contained in a state of not being impregnated into the glass fiber fabric, and the bromine concentration of the second resin layer was higher than the bromine concentration of the first resin layer, and the transparent sheet had a total light transmittance of 85% or more and a haze of 10% or less. Therefore, when the resin weight was increased, it was possible to more easily achieve both improved transparency and low total heat generation.

[0124] Among them, the transparent sheets of Examples 7 to 10 contain tetrabromobisphenol A, decabromodiphenyl ether or brominated vinyl ester in the first resin layer, and therefore have a lower radiation intensity of 50 kW / m on the surface of the sheet from a radiant electric heater as measured in accordance with "4.10.2 Heat generation test and evaluation method" in the "Fireproof and Evaluation Performance Testing and Evaluation Procedure Manual" (revised on March 1, 2014) of the General Incorporated Foundation Construction Materials Testing Center, compared to Examples 1 to 6, which contain phosphorus in the first resin layer. 2In a heat generation test in which radiant heat was applied, the first resin layer was less likely to blister, and for 20 minutes after the start of heating, cracks and holes that penetrate to the back surface, which are harmful from a fire prevention standpoint, were less likely to occur due to the blistering. [Explanation of symbols]

[0125] 1. Transparent sheet 2. Glass fiber fabric 3...1st resin layer 4...Second resin layer 5. Film layer

Claims

1. A transparent sheet comprising a plain woven glass fiber fabric and a resin, A first resin layer is included in the glass fiber fabric in a thickness direction of the transparent sheet, and a second resin layer is included in the glass fiber fabric without being impregnated therein, The second resin layer includes a curable resin containing a bromine atom as a substituent, or a curable resin containing a flame retardant containing a bromine atom, the second resin layer has a higher bromine concentration than the first resin layer; The transparent sheet has a total light transmittance of 85% or more and a haze of 10% or less. Transparent sheet.

2. In a heat generation test in which radiant heat of 50 kW / m2 is irradiated onto the surface of the sheet from a radiant electric heater, measured in accordance with "4.10.2 Heat Generation Test and Evaluation Method" in the "Fire Resistance Test and Evaluation Procedure Manual" (revised on March 1, 2014) of the General Incorporated Foundation Building Materials Testing Center, the total heat generation is 8 MJ / m 2 2. The transparent sheet according to claim 1, wherein:

3. The transparent sheet according to claim 1 , wherein the first resin layer is laminated on each of both sides of the second resin layer.

4. 4. The transparent sheet according to claim 1, wherein a total content of the resin contained in the first resin layer and the second resin layer is 200 g / m2 or more.

5. The transparent sheet according to any one of claims 1 to 4, wherein the total thickness of the first resin layer and the second resin layer is 180 µm or more.

6. The transparent sheet according to any one of claims 1 to 5, wherein the second resin layer contains a brominated vinyl ester resin.

7. The transparent sheet according to claim 6 , wherein the first resin layer contains tetrabromobisphenol A.

Citation Information

Patent Citations

  • Manufacture of flame-resisting resin board

    JP1981169066A

  • Polymerization inhibitor for acrylonitrile

    JP1989070454A

  • Transparent nonflammable sheet and its manufacturing method

    JP2005319746A

  • Glass fiber reinforced plastic material, glass fiber reinforced plastic prepreg, glass fiber reinforced plastic layer and LNG tank

    JP2007125745A

  • Transparent composite material

    JP2012219171A